Image forming apparatus, and image forming method

JP2025023761APending Publication Date: 2025-02-17FUJIFILM BUSINESS INNOVATION CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023128183
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0009】 <1>に係る発明によれば、背面層の硬度Haに対するエッジ層の硬度Hbの比率(Hb/Ha)が0.84未満又は0.93超であるクリーニングブレード、又はエッジ層の中間転写ベルトに接触する表面から200nm以内に存在するF及びSiの総量が、表面から5μm以内に存在するF及びSiの総量に対し75%未満であるクリーニングブレードを備える画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生、及び画像におけるホチキスマークの発生が抑制される画像形成装置が提供される。 <2>に係る発明によれば、トナー粒子の表面から800nm以内の領域に存在する離型剤がトナー粒子全体の離型剤の75%未満である画像形成装置に比べて、画像の低温定着性に優れた画像形成装置が提供される。 <3>に係る発明によれば、離型剤の融解温度が75℃超である画像形成装置に比べて、画像の低温定着性に優れた画像形成装置が提供され、離型剤の融解温度が70℃未満である画像形成装置に比べて、中間転写ベルト表面上でのトナーフィルミングの発生が抑制された画像形成装置が提供される。 <4>に係る発明によれば、背面層の硬度Haに対するエッジ層の硬度Hbの比率(Hb/Ha)が0.87未満又は0.90超であるクリーニングブレードを備える画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生が抑制される画像形成装置が提供される。 <5>又は<6>に係る発明によれば、エッジ層の硬度が85°以上であるクリーニングブレード又は背面層の硬度が95°超であるクリーニングブレードを備える画像形成装置に比べて、画像におけるホチキスマークの発生が抑制された画像形成装置が提供され、エッジ層の硬度が75°未満であるクリーニングブレードを備える画像形成装置に比べて、優れたクリーニング性が達成されかつクリーニングブレードの摩耗が抑制された画像形成装置が提供され、背面層の硬度が85°未満であるクリーニングブレードを備える画像形成装置に比べて、クリーニングブレードにおけるめくれの発生が抑制された画像形成装置が提供される。 <7>に係る発明によれば、エッジ層の中間転写ベルトに接触する表面から200nm以内に存在するF及びSiの総量が、表面から5μm以内に存在するF及びSiの総量に対し85%未満であるクリーニングブレードを備える画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生が抑制される画像形成装置が提供される。 <8>又は<9>に係る発明によれば、エッジ層の中間転写ベルトに接触する表面に存在するF及びSiの総量が15atm%未満であるクリーニングブレードを備える画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生が抑制される画像形成装置が提供される。 <10>又は<11>に係る発明によれば、エッジ層の中間転写ベルトに接触する表面から50nmの位置に存在するF及びSiの総量が0.3atm%未満であるクリーニングブレードを備える画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生が経時においても抑制される画像形成装置が提供される。 <12>に係る発明によれば、エッジ層の中間転写ベルトに接触する表層にシリコーン系ポリマーを含まず、フッ素系化合物を含むクリーニングブレードを備える画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生が抑制される画像形成装置が提供される。 <13>に係る発明によれば、クリーニングブレードが中間転写ベルトに対して1.5gf/mm未満の押し付け圧で接触する画像形成装置に比べて、画像におけるホチキスマークの発生がより抑制される画像形成装置が提供され、クリーニングブレードが中間転写ベルトに対して3.5gf/mm超の押し付け圧で接触する画像形成装置に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生がより抑制される画像形成装置が提供される。 <14>に係る発明によれば、背面層の硬度Haに対するエッジ層の硬度Hbの比率(Hb/Ha)が0.84未満又は0.93超であるクリーニングブレード、又はエッジ層の中間転写ベルトに接触する表面から200nm以内に存在するF及びSiの総量が、表面から5μm以内に存在するF及びSiの総量に対し75%未満であるクリーニングブレードを用いたクリーニング工程を有する画像形成方法に比べて、中間転写ベルトの表面におけるトナーフィルミングの発生、及び画像におけるホチキスマークの発生が抑制される画像形成方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023761000001_ABST
    Figure 2025023761000001_ABST
Patent Text Reader

Abstract

To provide an image forming apparatus that prevents the occurrence of toner filming on a surface of an intermediate transfer belt and the occurrence of a stapler mark in an image.SOLUTION: An image forming apparatus comprises: developing means that develops a toner image with a developer in which a mold release agent present within 800 nm from a surface of a toner particle is 70% or more of the entire mold release agent, and in which a melting temperature of the mold release agent is 65°C or more and 80°C or less; an intermediate transfer belt; and a cleaning device that has a cleaning blade which cleans the intermediate transfer belt and has a two-layer structure formed of an edge layer and a rear face layer, and in which a ratio of the hardness of the edge layer to the hardness of the rear face layer is 0.84 or more and 0.93 or less, and an amount of F and Si within 200 nm from a surface in contact with the intermediate transfer belt accounts for 75% or more of an amount of F and Si within 5 μm from the surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an image forming apparatus and an image forming method. [Background technology]

[0002] In an image forming apparatus using an electrophotographic method (such as a copier, a facsimile, or a printer), a toner image formed on the surface of an image carrier is transferred to the surface of a recording medium and fixed on the recording medium to form an image. Note that, for example, an intermediate transfer belt is used to transfer the toner image to the recording medium, and a cleaning blade is used to clean the outer peripheral surface of the intermediate transfer belt.

[0003] For example, Patent Document 1 discloses an image forming apparatus including: "an image carrier; a charging means for charging a surface of the image carrier; a latent image forming means for forming an electrostatic latent image on the charged surface of the image carrier; a developing means for developing the electrostatic latent image formed on the surface of the image carrier into a toner image; a transfer means for transferring the toner image on the surface of the image carrier to a transfer body; and a cleaning means having a cleaning blade that comes into contact with the surface of the image carrier and cleans the transfer residual toner adhering to the surface of the image carrier, the cleaning blade having a rectangular elastic blade and a surface layer that covers a ridgeline of a tip end of the elastic blade, is harder than the elastic blade, and has a friction coefficient of 0.1 or more and 0.6 or less; the image carrier has a surface protective layer in which fluororesin fine particles are dispersed, and the surface protective layer is formed by dispersing fluororesin fine particles having a volume average particle size of 10 μm or less, and then applying a coating liquid obtained by irradiating the dispersed fluororesin fine particles with ultrasonic waves."

[0004] Patent Document 2 describes a process cartridge having an image carrier, a developing unit which develops an electrostatic latent image formed on the image carrier with a toner to form a visible image, and a cleaning unit which removes residual toner remaining on the image carrier with a cleaning blade, the cleaning blade having an elastic member which comes into contact with the surface of the image carrier to remove the residual toner remaining on the image carrier, the elastic member having a base material and a surface layer provided on the base material, the surface layer having a front surface and a rear surface, the front surface being a surface of the base material facing the downstream side in the traveling direction of the image carrier from the contact portion of the elastic member which comes into contact with the image carrier, the front surface being a surface of the base material facing the downstream side in the traveling direction of ... The surface layer is formed on at least a part of the lower surface of the substrate including the contact portion, and the surface layer has a hardness gradient in which the Martens hardness HM measured using a nanoindenter decreases from the surface to the lower surface of the substrate in the film thickness direction, and the Martens hardness HM measured at a load of 1 μN and at a load of 1000 μN is 2.5 N / mm2 or more and 32.5 N / mm2 or less, the average film thickness of the surface layer at the contact portion is 10 μm or more and 500 μm or less, and the toner provided in the developing means has a circularity of less than 0.950 and a fine powder content of 2 μm or less is 20% by number or more and 60% by number or less.

[0005] Patent Document 3 discloses "a cleaning blade formed by cutting a plate-like body made of a cured polyurethane resin composition, in which an end face of the cleaning blade formed by the above cutting has 4 atom % or more of silicon atoms (Si) present due to the adhesion of an organosiloxane and an oxygenation treatment." [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-300751 A [Patent Document 2] Patent Publication No. 2021-012342 [Patent Document 3] JP 2001-051565 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present disclosure is to provide an image forming apparatus and an image forming method in which the occurrence of toner filming on the surface of an intermediate transfer belt and the occurrence of staple marks in an image are suppressed compared to image forming apparatuses and image forming methods equipped with a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer is less than 0.84 or exceeds 0.93, or in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Means for solving the problem]

[0008] Means for solving the above problems include the following aspects. <1> An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; an intermediate transfer belt onto whose outer circumferential surface the toner image is transferred; a primary transfer means having a primary transfer member for primarily transferring the toner image formed on the surface of an image carrier onto an outer peripheral surface of the intermediate transfer belt; a secondary transfer unit having a secondary transfer member for secondarily transferring the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; a cleaning device having a cleaning blade which comes into contact with and cleans the outer peripheral surface of the intermediate transfer belt, the cleaning blade having a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer being made of polyurethane resin, the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer being 0.84 or more and 0.93 or less, and the total amount of F and Si present within 200 nm from the surface of the edge layer which comes into contact with the intermediate transfer belt being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising: <2> the amount of the release agent present within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle; <1> 2. The image forming apparatus according to claim 1 . <3> The melting temperature of the release agent is 70° C. or higher and 75° C. or lower. <1> or <2> 2. The image forming apparatus according to claim 1 . <4> The cleaning blade has a ratio (Hb / Ha) of a hardness Hb of the edge layer to a hardness Ha of the back layer of 0.87 or more and 0.90 or less. <1> ~ <3> 13. The image forming apparatus according to claim 12, <5> The hardness Hb of the edge layer is 75° or more and less than 85°, and the hardness Ha of the back layer is 85° or more and 95° or less. <1> ~ <4> 13. The image forming apparatus according to claim 12, <6> The hardness Hb of the edge layer is 77° or more and 83° or less, and the hardness Ha of the back layer is 87° or more and 93° or less. <5> 2. The image forming apparatus according to claim 1 . <7> the cleaning blade, the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface; <1> ~ <6> 13. The image forming apparatus according to claim 12, <8> the cleaning blade has an edge layer having a surface that comes into contact with the intermediate transfer belt, and the total amount of F and Si present on the surface of the edge layer is 5 atm % or more. <1> ~ <7> 13. The image forming apparatus according to claim 12, <9> the cleaning blade has an edge layer having a surface contacting the intermediate transfer belt and a total amount of F and Si present thereon of 18 atm % or more and 25 atm % or less; <8> 2. The image forming apparatus according to claim 1 . <10> the cleaning blade has an edge layer having a total amount of F and Si present at a position 50 nm from the surface that contacts the intermediate transfer belt of 0.3 atm % or more; <1> ~ <9> 13. The image forming apparatus according to claim 12, <11> the cleaning blade has an edge layer having a total amount of F and Si present at a position 50 nm from the surface that contacts the intermediate transfer belt of 0.3 atm % or more and 2.0 atm % or less; <10> 2. The image forming apparatus according to claim 1 . <12> the cleaning blade includes a silicone-based polymer in a surface layer of the edge layer that contacts the intermediate transfer belt; <1> ~ <11> 13. The image forming apparatus according to claim 12, <13> the cleaning blade is brought into contact with the intermediate transfer belt at a pressing pressure of 1.5 gf / mm or more and 3.5 gf / mm or less; <1> ~ <12> 13. The image forming apparatus according to claim 12, <14> a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 60° C. or more and 80° C. or less; a primary transfer step of primarily transferring the toner image formed on the surface of an image carrier onto an outer peripheral surface of an intermediate transfer belt; a secondary transfer step of secondary transferring the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; a cleaning step of contacting an outer peripheral surface of the intermediate transfer belt with a cleaning blade having a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer being made of polyurethane resin, the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer being 0.84 or more and 0.93 or less, and the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising: Effect of the Invention

[0009] <1> According to the invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of the intermediate transfer belt and the occurrence of staple marks in an image are suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.84 or exceeds 0.93, or in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. <2> According to the present invention, an image forming apparatus is provided that has excellent low-temperature fixing ability of images compared to an image forming apparatus in which the release agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle. <3> According to the invention, an image forming apparatus is provided which has excellent low-temperature image fixing ability compared to an image forming apparatus in which the melting temperature of the release agent is higher than 75°C, and an image forming apparatus is provided in which the occurrence of toner filming on the intermediate transfer belt surface is suppressed compared to an image forming apparatus in which the melting temperature of the release agent is lower than 70°C. <4> According to the present invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of an intermediate transfer belt is suppressed compared to an image forming apparatus equipped with a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.87 or exceeds 0.90. <5> or <6> According to the invention, an image forming device is provided in which the occurrence of staple marks in an image is suppressed compared to an image forming device equipped with a cleaning blade whose edge layer has a hardness of 85° or more or a cleaning blade whose back layer has a hardness of more than 95°, an image forming device is provided in which excellent cleaning performance is achieved and wear of the cleaning blade is suppressed compared to an image forming device equipped with a cleaning blade whose edge layer has a hardness of less than 75°, and an image forming device is provided in which curling of the cleaning blade is suppressed compared to an image forming device equipped with a cleaning blade whose back layer has a hardness of less than 85°. <7> According to the invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of an intermediate transfer belt is suppressed compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 85% of the total amount of F and Si present within 5 μm from the surface. <8> or <9> According to the present invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present on the surface of the edge layer that contacts the intermediate transfer belt is less than 15 atm %. <10> or <11> According to the present invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of an intermediate transfer belt is suppressed over time, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 0.3 atm %. <12> According to the invention, an image forming apparatus is provided in which the surface layer of the edge layer that comes into contact with the intermediate transfer belt does not contain a silicone-based polymer, and the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed compared to an image forming apparatus equipped with a cleaning blade that contains a fluorine-based compound. <13> According to the invention, an image forming apparatus is provided in which the occurrence of staple marks in an image is more effectively suppressed than in an image forming apparatus in which a cleaning blade contacts the intermediate transfer belt with a pressing pressure of less than 1.5 gf / mm, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the intermediate transfer belt is more effectively suppressed than in an image forming apparatus in which a cleaning blade contacts the intermediate transfer belt with a pressing pressure of more than 3.5 gf / mm. <14> According to the invention, there is provided an image forming method which suppresses the occurrence of toner filming on the surface of the intermediate transfer belt and staple marks in an image, as compared to an image forming method having a cleaning step using a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.84 or exceeds 0.93, or a cleaning blade in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] 11 is a schematic diagram for explaining a bite amount d of a cleaning blade into an intermediate transfer belt. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the present embodiment, which is an example of the present disclosure, will be described. These descriptions and examples are merely illustrative of the embodiment, and do not limit the scope of the embodiment.

[0012] In the numerical ranges described in the present embodiment, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described in the present embodiment. In addition, in the numerical ranges described in the present embodiment, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In this embodiment, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. When the embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this. In this embodiment, each component may contain multiple types of corresponding substances. When referring to the amount of each component in the composition in this embodiment, if multiple substances corresponding to each component are present in the composition, the amount refers to the total amount of the multiple substances present in the composition, unless otherwise specified.

[0013] [Image forming device] The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for accommodating an electrostatic image developer containing a toner having toner particles and for developing the electrostatic image formed on the surface of the image carrier by the electrostatic image developer as a toner image, an intermediate transfer belt having a toner image transferred onto its outer circumferential surface, a primary transfer means having a primary transfer member for primarily transferring the toner image formed on the surface of the image carrier onto the outer circumferential surface of the intermediate transfer belt, a secondary transfer means having a secondary transfer member for secondarily transferring the toner image primarily transferred onto the outer circumferential surface of the intermediate transfer belt onto the surface of a recording medium, and a cleaning device having a cleaning blade for contacting and cleaning the outer circumferential surface of the intermediate transfer belt. The toner particles have a releasing agent present in a region within 800 nm from the surface that accounts for 70% or more of the releasing agent in the entire toner particle, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less. The cleaning blade has a two-layer structure consisting of an edge layer and a back layer, and the edge layer and the back layer are made of polyurethane resin. The ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer is 0.84 to 0.93. Furthermore, the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.

[0014] The image forming apparatus according to the present embodiment, with the above-described configuration, is able to suppress the occurrence of toner filming on the surface of the intermediate transfer belt and the occurrence of staple marks in the image. The reason for this is believed to be as follows.

[0015] From the viewpoint of improving the low-temperature fixability of images, the use of toner particles having low melting temperature wax unevenly distributed on the surface, specifically, a toner in which the release agent present in the region within 800 nm from the surface of the toner particles is 70% or more of the release agent of the entire toner particle, and the melting temperature of the release agent is 65°C or more and 80°C or less, has been considered. However, when toner particles having low melting temperature wax unevenly distributed on the surface are used, toner filming tends to occur on the surface of the intermediate transfer belt when images with low image density are repeatedly formed in a high-temperature and high-humidity environment. This is considered to be because the toner particles having low melting temperature wax unevenly distributed on the surface as described above become soft and easily crushed in a high-temperature and high-humidity environment. Furthermore, it is considered that the pressure applied by the cleaning blade to each toner particle increases as the toner particles present on the intermediate transfer belt are reduced by repeatedly forming images with low image density. In response to this, a method of suppressing the occurrence of toner filming can be considered by adjusting the cleaning blade pressed against the intermediate transfer belt. For example, a method of suppressing toner filming can be exemplified by increasing the hardness of the cleaning blade to improve scraping performance. However, when the hardness of the cleaning blade is increased to improve scraping performance, the ability of the cleaning blade to follow the opposing surface decreases, and as a result, staple marks may occur in the formed image. Note that a staple mark refers to an image defect in which two high-density dots appear side by side on an image in a direction (width direction) perpendicular to the process direction (i.e., the same as the running direction of the intermediate transfer belt and the transport direction of the recording medium).

[0016] In contrast, the image forming apparatus according to the present embodiment uses a cleaning blade in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface. In other words, F and Si are unevenly distributed in the cleaning blade near the contact portion with the intermediate transfer belt. The presence of at least one of F and Si in the contact portion reduces the friction of the cleaning blade, and stabilizes the behavior at the tip of the contact portion. As a result, even when toner particles having a low melting temperature wax unevenly distributed on the surface layer as described above are used, the occurrence of toner filming on the surface of the intermediate transfer belt when low image density images are repeatedly formed in a high temperature and high humidity environment is suppressed. In addition, the image forming apparatus according to the present embodiment uses a cleaning blade having a two-layer structure consisting of an edge layer and a back layer, and the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer is 0.84 or more and 0.93 or less. In other words, a cleaning blade having a two-layer structure in which the back layer is harder than the edge layer is used, which improves the ability of the cleaning blade to follow the opposing surface. As a result, the occurrence of staple marks in the formed image is suppressed.

[0017] From the above, it is presumed that the image forming apparatus according to this embodiment suppresses the occurrence of toner filming on the surface of the intermediate transfer belt and the occurrence of staple marks in images.

[0018] (toner) The toner contained in the electrostatic image developer used in the image forming apparatus according to this embodiment will be described. The toner contains toner particles, and the release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particle, and the melting temperature of the release agent is 65°C or more and 80°C or less.

[0019] The toner particles contain a release agent, and may further contain a binder resin. The toner particles may also contain other internal additives such as a colorant.

[0020] -Release agent- The melting temperature of the release agent is 65° C. to 80° C., preferably 68° C. to 77° C., and more preferably 70° C. to 75° C. When the melting temperature of the release agent is 80° C. or less, the low-temperature fixing property of the image can be improved. On the other hand, when the melting temperature of the release agent is 65° C. or more, the occurrence of toner filming on the transfer belt surface can be suppressed.

[0021] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining the melting temperature in JIS K-7121-1987 "Method for measuring transition temperature of plastics."

[0022] More than 70% of the total release agent is present within 800 nm from the surface of the toner particles (hereinafter, the proportion of the release agent present within 800 nm from the surface of the toner particles is also referred to as the "surface proportion of the release agent"). The surface layer ratio of the release agent is 70% or more, preferably 75% or more, and more preferably 80% or more. The upper limit of the surface layer ratio of the release agent is preferably 100%. By making the surface layer ratio of the release agent 70% or more, the low temperature fixability of the image can be improved.

[0023] Here, a method for measuring the surface layer proportion of the release agent will be described. Samples and images for measurement are prepared in the following manner. The toner is mixed and embedded in an epoxy resin, and the epoxy resin is solidified. The solidified product is cut by an ultramicrotome device (UltracutUCT manufactured by Leica) to prepare a thin specimen having a thickness of 80 nm to 130 nm. Then, an SEM image of the thin specimen is obtained by an ultra-high resolution field emission scanning electron microscope (FE-SEM, S-4800 manufactured by Hitachi High-Technologies Corporation). In the SEM image, a cross section of a toner particle whose maximum length is 85% or more of the volume average particle diameter of the toner particle is selected, the domain of the release agent is observed, the area of ​​the release agent of the entire toner particle and the area of ​​the release agent present in the region within 800 nm from the surface of the toner particle are obtained, and the ratio of the two areas (area of ​​the release agent present in the region within 800 nm from the surface of the toner particle / area of ​​the release agent of the entire toner particle) is calculated. Then, this calculation is performed for 100 toner particles, and the average value is taken as the surface layer ratio of the release agent. The reason for selecting a toner particle cross section whose maximum length is 85% or more of the volume average particle diameter of the toner particle is that a cross section that is less than 85% of the volume average particle diameter is expected to be a cross section of the end of a toner particle, and the cross section of the end of a toner particle does not well reflect the state of the domains in the toner particle.

[0024] As a method for controlling the surface layer ratio of the release agent to 70% or more, for example, there is a method in which the toner particles have a core-shell structure and the release agent is used when forming the shell.

[0025] Examples of the release agent include hydrocarbon waxes such as paraffin wax, natural waxes such as carnauba wax, rice wax, candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, ester waxes such as fatty acid esters and montan acid esters, etc. The release agent is not limited to these. As the release agent, for example, a hydrocarbon wax is preferably used. The hydrocarbon wax is a wax having a hydrocarbon skeleton, and examples thereof include Fischer-Tropsch wax, polyethylene wax (wax having a polyethylene skeleton), polypropylene wax (wax having a polypropylene skeleton), paraffin wax (wax having a paraffin skeleton), and microcrystalline wax. Among these, from the viewpoint of fixability, the hydrocarbon wax is preferably Fischer-Tropsch wax, polyethylene wax, or polypropylene wax. In addition, from the viewpoint of fixability, it is preferable that a plurality of kinds of hydrocarbon waxes are contained in the toner particles. The proportion of the hydrocarbon wax in the total release agent is 85% by mass or more, preferably 95% by mass or more, and more preferably 100% by mass.

[0026] The content of the release agent is, for example, preferably from 1% by mass to 20% by mass, more preferably from 3% by mass to 20% by mass, even more preferably from 3% by mass to 15% by mass, and even more preferably from 5% by mass to 15% by mass, based on the total amount of the toner particles.

[0027] -Binding resin- As the binder resin, for example, a polyester resin is preferably used. The ratio of the polyester resin to the total binder resin is, for example, 75% by mass or more, preferably 90% by mass or more, and more preferably 100% by mass.

[0028] The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.

[0029] The "crystalline" nature of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.

[0030] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. The amorphous polyester resin may be a commercially available product or a synthesized product.

[0031] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0032] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0033] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."

[0034] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0035] The amorphous polyester resin can be obtained by a known manufacturing method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0036] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. The crystalline polyester resin may be a commercially available product or a synthesized product. Here, the crystalline polyester resin is preferably a polycondensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group, since the crystalline polyester resin can easily form a crystalline structure.

[0037] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0038] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0039] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.

[0040] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0041] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0042] The crystalline polyester resin can be obtained by a known manufacturing method, for example, in the same manner as the amorphous polyester.

[0043] Here, the binder resin may be used in combination with the polyester resin, and preferably includes a styrene (meth)acrylic resin.

[0044] -Styrene (meth)acrylic resin- Styrene (meth)acrylic resin is a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth)acryloyl group. "(meth)acrylic acid" is an expression that includes both "acrylic acid" and "methacrylic acid". Also, "(meth)acryloyl group" is an expression that includes both "acryloyl group" and "methacryloyl group".

[0045] Examples of monomers having a styrene skeleton (hereinafter referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more. Of these, as the styrene-based monomer, styrene is preferred from the viewpoints of ease of reaction, ease of reaction control, and availability.

[0046] Examples of monomers having a (meth)acryloyl group (hereinafter referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl esters (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, amyl (meth)acrylate, Examples of the (meth)acrylate include neopentyl acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate esters (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and (meth)acrylamide. The (meth)acrylic acid monomers may be used alone or in combination of two or more.

[0047] The copolymerization ratio of the styrene monomer to the (meth)acrylic monomer (mass basis, styrene monomer / (meth)acrylic monomer) may be, for example, 85 / 15 to 70 / 30.

[0048] The styrene (meth)acrylic resin preferably has a crosslinked structure in terms of suppressing image offset. Examples of the styrene (meth)acrylic resin having a crosslinked structure include a crosslinked product obtained by copolymerizing at least a monomer having a styrene skeleton, a monomer having a (meth)acrylic acid skeleton, and a crosslinkable monomer.

[0049] The crosslinkable monomer may, for example, be a bifunctional or higher functional crosslinking agent. Examples of bifunctional crosslinking agents include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylene bis(meth)acrylamide, decanediol diacrylate, glycidyl (meth)acrylate, etc.), polyester type di(meth)acrylate, 2-([1'-methylpropylideneamino]carboxyamino)ethyl methacrylate, etc. Examples of polyfunctional crosslinking agents include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., tetramethylolmethane tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl asocyanurate, triallyl isocyanurate, triallyl trimellitate, diaryl chlorendate, etc.

[0050] The copolymerization ratio of the crosslinkable monomer to the total monomers (mass basis, crosslinkable monomer / total monomers) may be, for example, 2 / 1000 to 30 / 1000.

[0051] The weight average molecular weight of the styrene (meth)acrylic resin is, for example, from 30,000 to 200,000, preferably from 40,000 to 100,000, and more preferably from 50,000 to 80,000, in terms of suppressing image offset. The weight average molecular weight of the styrene (meth)acrylic resin is a value measured by the same method as that for the weight average molecular weight of the polyester resin.

[0052] The content of the styrene (meth)acrylic resin is, for example, from 10% by mass to 30% by mass, preferably from 12% by mass to 28% by mass, and more preferably from 15% by mass to 25% by mass, in terms of achieving both the fluidity and storage stability of the toner and the suppression of image offset, relative to the toner particles.

[0053] Furthermore, other binder resins may be used in combination as the binder resin. Other binder resins include, for example, vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers made of a combination of two or more of these monomers. Examples of other binder resins include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the presence of these. These other binder resins may be used alone or in combination of two or more kinds.

[0054] The content of the binder resin is, for example, preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total amount of the toner particles.

[0055] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0056] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0057] The content of the colorant is, for example, preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0058] -Other additives- Examples of other additives in the toner include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0059] -Characteristics of toner particles- The toner particles may be toner particles of a single layer structure, or may be toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) that coats the core, and the core-shell structure is preferable. The toner particles of the core-shell structure are preferably composed of, for example, a core composed of a binder resin and a colorant, and a coating layer composed of a binder resin and a release agent.

[0060] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.

[0061] Various average particle sizes and various particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and the number particle size D84p. Using these, the volume average particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number average particle size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:

[0062] The shape factor SF1 of the toner particles is preferably 110 or more and 150 or less, and more preferably 120 or more and 140 or less.

[0063] The shape factor SF1 is calculated by the following formula. Formula: SF1=(ML 2 / A)×(π / 4)×100 In the above formula, ML represents the absolute maximum length of the toner, and A represents the projected area of ​​the toner. Specifically, the shape factor SF1 is quantified mainly by analyzing a microscope image or a scanning electron microscope image using an image analyzer, and is calculated as follows: That is, an optical microscope image of particles scattered on the surface of a slide glass is captured by a video camera into a Luzex image analyzer, the maximum length and projected area of ​​100 particles are determined, and the above formula is used to calculate the average value.

[0064] -External additives- The toner may further contain an external additive in addition to the toner particles. Examples of the external additive include inorganic particles, such as SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.

[0065] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobic treatment agent is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0066] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).

[0067] The amount of the external additive added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.

[0068] -Toner manufacturing method- The toner used in the image forming apparatus according to the present embodiment is produced by producing toner particles, and then, when an external additive is contained, externally adding the external additive to the toner particles.

[0069] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and well-known production methods are used. Among them, it is preferable to obtain the toner particles by the aggregation and coalescence method.

[0070] Each step of the aggregation and coalescence method will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant will be described, but the colorant is used as necessary. Of course, additives other than the colorant may be used.

[0071] ·Resin particle dispersion preparation process First, a resin particle dispersion liquid in which polyester resin particles serving as a binder resin are dispersed, a colorant dispersion liquid in which colorant particles are dispersed, and a release agent particle dispersion liquid in which release agent particles are dispersed are prepared.

[0072] The polyester resin particle dispersion liquid is prepared, for example, by dispersing polyester resin particles in a dispersion medium with the aid of a surfactant.

[0073] The dispersion medium used in the polyester resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water; alcohols; etc. These may be used alone or in combination of two or more.

[0074] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0075] Examples of methods for dispersing polyester resin particles in a dispersion medium include general dispersion methods using a rotary shear homogenizer, a ball mill with media, a sand mill, a dyno mill, etc. Alternatively, polyester resin particles may be dispersed in a dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then water (W phase) is added to invert the phase from W / O to O / W, dispersing the resin in particulate form in an aqueous medium.

[0076] The volume average particle size of the polyester resin particles dispersed in the polyester resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle diameter of the polyester resin particles is determined by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), drawing a cumulative distribution for the volume of the divided particle size range (channel) from the small particle size side, and determining the particle size that accounts for 50% by volume of all particles as the volume average particle diameter D50v. The volume average particle diameters of particles in other dispersions are also measured in the same manner.

[0077] The content of the polyester resin particles contained in the polyester resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0078] The colorant dispersion and the release agent particle dispersion are also prepared in the same manner as the polyester resin particle dispersion. That is, the dispersion medium, the dispersion method, the volume average particle size of the particles, and the content of the particles in the polyester resin particle dispersion are the same for the colorant dispersion and the release agent particle dispersion.

[0079] ·First agglomerated particle formation step Next, the polyester resin particle dispersion and the colorant dispersion are mixed. Then, in the mixed dispersion, the polyester resin particles and the colorant particles are hetero-aggregated to form first aggregate particles containing the polyester resin particles and the colorant particles and having a diameter close to that of the target toner particles. If necessary, a release agent particle dispersion may also be mixed to cause the first aggregate particles to contain release agent particles.

[0080] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the polyester resin (specifically, for example, −30° C. or more and −10° C. or less of the glass transition temperature of the polyester resin), and the particles dispersed in the mixed dispersion are aggregated to form first aggregated particles. In the first aggregate particle formation step, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.

[0081] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the flocculant used is reduced, and the charging characteristics are improved. An additive that forms a complex or a similar bond with the metal ions of the flocculant may be used together with the flocculant, and a chelating agent is preferably used as this additive.

[0082] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.

[0083] ·Second agglomerated particle formation process After obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the first aggregated particle dispersion, the polyester resin particle dispersion, and the release agent particle dispersion are further mixed. The polyester resin particle dispersion and the release agent particle dispersion may be mixed in advance, and the mixture may be mixed into the first aggregated particle dispersion.

[0084] Then, in the mixed dispersion liquid in which the first aggregated particles, polyester resin particles, and release agent particles are dispersed, the polyester resin particles and release agent particles are aggregated so as to adhere to the surfaces of the first aggregated particles, thereby forming second aggregated particles.

[0085] Specifically, for example, in the first aggregate particle forming step, when the first aggregate particles reach a target particle size, a dispersion in which polyester resin particles and release agent particles are dispersed is mixed into the first aggregate particle dispersion, and then the mixed dispersion is heated at a temperature equal to or lower than the glass transition temperature of the polyester resin, and the pH of the mixed dispersion is adjusted to, for example, a range of about 6.5 to 8.5 to stop the progress of aggregation.

[0086] As a result, second aggregated particles are obtained, which are aggregated such that the polyester resin particles and the release agent particles adhere to the surfaces of the first aggregated particles.

[0087] ·Fusion / coalescence process Next, the second aggregate particle dispersion liquid in which the second aggregate particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the polyester resin (for example, a temperature 10° C. to 50° C. higher than the glass transition temperature of the polyester resin) to fuse and coalesce the second aggregate particles, thereby forming toner particles.

[0088] Through the above steps, toner particles are obtained. Note that the toner particles may be produced through a process in which, after obtaining the second aggregated particle dispersion in which the second aggregated particles are dispersed, the second aggregated particle dispersion is further mixed with a polyester resin particle dispersion in which polyester resin particles are dispersed, and the polyester resin particles are aggregated so that the polyester resin particles are further attached to the surfaces of the second aggregated particles, thereby forming third aggregated particles, and a process in which the third aggregated particle dispersion in which the third aggregated particles are dispersed is heated to fuse and coalesce the third aggregated particles, thereby forming toner particles.

[0089] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dry toner particles. In the washing step, from the viewpoint of electrostatic chargeability, it is preferable to carry out sufficient replacement washing with ion-exchanged water. In addition, the solid-liquid separation step is not particularly limited, but from the viewpoint of productivity, it is preferable to carry out suction filtration, pressure filtration, etc. In addition, in the drying step, there is no particular limit to the method, but from the viewpoint of productivity, it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.

[0090] The toner according to the present embodiment is produced, for example, by adding an external additive to dry toner particles and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.

[0091] -Electrostatic image developer- In this embodiment, the electrostatic image developer contained in the developing unit contains at least the above-mentioned toner. The electrostatic image developer may be a one-component developer containing only the toner, or may be a two-component developer in which the toner is mixed with a carrier.

[0092] The carrier is not particularly limited, and may be a known carrier. For example, the carrier may be a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin; a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin; etc. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material, and the surface of the carrier is coated with a resin.

[0093] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.

[0094] Examples of the conductive particles include metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0095] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing organosiloxane bonds or modified products thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The coating resin and matrix resin may contain additives such as conductive materials.

[0096] To coat the surface of the core material with a resin, a method of coating with a coating layer forming solution in which the coating resin and various additives (used as necessary) are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited, and may be selected taking into consideration the type of resin used, coating suitability, etc. Specific resin coating methods include an immersion method in which the core material is immersed in the coating layer forming solution; a spray method in which the coating layer forming solution is sprayed on the core material surface; a fluidized bed method in which the coating layer forming solution is sprayed on the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the coating layer forming solution are mixed in a kneader coater and then the solvent is removed; and the like.

[0097] The mixture ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0098] (cleaning blade) The cleaning blade used in the image forming apparatus according to the present embodiment will be described. The cleaning blade has a two-layer structure consisting of an edge layer and a back layer, and the edge layer and the back layer are made of polyurethane resin. The cleaning blade has a ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer of 0.84 to 0.93. In addition, the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.

[0099] -Ratio (Hb / Ha)- The cleaning blade has a ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer of 0.84 or more and 0.93 or less. When the ratio (Hb / Ha) is within the above range, the cleaning blade is improved in conformity with the opposing surface, and the occurrence of staple marks in the formed image is suppressed. The ratio (Hb / Ha) is more preferably 0.87 or more and 0.90 or less, and more preferably 0.88 or more and 0.89 or less.

[0100] -Hardness of edge layer and back layer- The hardness Ha of the back layer is preferably 85° or more and 95° or less, more preferably 87° or more and 93° or less, and even more preferably 89° or more and 91° or less. When the hardness of the back layer is 85° or more, the occurrence of curling in the cleaning blade is suppressed. When the hardness of the back layer is 95° or less, the conformability of the cleaning blade to the opposing surface is further improved.

[0101] The hardness Hb of the edge layer is preferably 75° or more and less than 85°, more preferably 77° or more and less than 83°, and even more preferably 79° or more and less than 81°. When the hardness of the edge layer is 75° or more, excellent cleaning properties are achieved and wear of the cleaning blade is suppressed. When the hardness of the edge layer is less than 85°, the conformity of the cleaning blade to the opposing surface is further improved.

[0102] The hardness of each layer in the cleaning blade is measured by the following method. The hardness is measured according to the hardness test method specified in JIS K6253 (1997) using a type A durometer specified in JIS K7215 (1986). Specifically, a type A durometer (manufactured by Kobunshi Keisokuki) specified in JIS K7215 (1986) is used, the indenter is pressed against the contact area, and the maximum value of the pointer is read within one second. This measurement is then repeated five times, and the JIS-A hardness of the contact area is calculated from the average value. In addition, when the contact portion of the edge layer of the cleaning blade is modified as described below, the portion modified is the object of the measurement of the hardness, but it is considered that the hardness is almost the same between the portion modified and the portion not modified.

[0103] - Surface layer ratio of F and Si - The cleaning blade has a ratio (surface layer ratio of F and Si) of the total amount of F and Si present within 200 nm from the surface (contact portion) of the edge layer that contacts the intermediate transfer belt to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) of 75% or more. When the surface layer ratio of F and Si at the contact portion of the cleaning blade is 75% or more, the behavior of the tip of the contact portion of the cleaning blade is stabilized, and the occurrence of toner filming on the intermediate transfer belt surface is suppressed. The surface layer ratio of F and Si at the contact portion of the cleaning blade is more preferably 85% or more, and more preferably 90% or more.

[0104] - Surface F and Si content - The cleaning blade has an edge layer with a total amount of F and Si (surface F and Si amount) of 15 atm% or more on the surface (contact portion) of the cleaning blade that contacts the intermediate transfer belt, more preferably 18 atm% or more, and even more preferably 20 atm% or more. When the surface F and Si amount at the contact portion of the cleaning blade is 15 atm% or more, the behavior of the tip of the contact portion of the cleaning blade is more stabilized, and the occurrence of toner filming on the intermediate transfer belt surface is more suppressed. The upper limit of the surface F and Si content at the contact portion of the cleaning blade is not particularly limited, but from the viewpoint of suppressing poor cleaning caused by a belly-contact state resulting from insufficient tack at the tip portion due to a decrease in the friction coefficient, the upper limit is preferably 25 atm % or less, and more preferably 22 atm % or less.

[0105] -50nm position F and Si amount- The cleaning blade has a total amount of F and Si (amount of F and Si at 50 nm) of 0.3 atm% or more, more preferably 0.5 atm% or more, and even more preferably 1.0 atm% or more, present at a position 50 nm from the surface (contact portion) of the edge layer that contacts the intermediate transfer belt. By having the amount of F and Si at 50 nm of the cleaning blade of 0.3 atm% or more, low friction at the contact portion of the cleaning blade is maintained, and the occurrence of toner filming on the intermediate transfer belt surface is suppressed over time. The upper limit of the cleaning blade's 50 nm position F and Si content is not particularly limited, but from the viewpoint of suppressing local wear, it is preferably 7 atm % or less, and more preferably 5 atm % or less.

[0106] A method for measuring the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the edge layer of a cleaning blade that contacts an intermediate transfer belt to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) will be described. That is, a method for analyzing the amount of F element and the amount of Si element in the depth direction from the contact portion in the edge layer of a cleaning blade will be described. A region including the surface (contact portion) of the edge layer of the cleaning blade that comes into contact with the intermediate transfer belt is cut out, and the amounts (atm%) of N, C, O, F, and Si elements are measured in the depth direction from the contact portion using XPS (Versa Probe II manufactured by Ulvac-PHI).

[0107] The total amount of F and Si present on the surface (contact portion) of the edge layer of the cleaning blade that comes into contact with the intermediate transfer belt is determined by plotting the depth from the contact portion of the cleaning blade obtained by the above-mentioned analysis in the depth direction versus element ratio, with the area up to a depth of 5 μm being SA and the area up to a depth of 200 nm being SB, and calculating the ratio from the formula SB / SA × 100. The total amount of F and Si present at a position 50 nm from the surface (contact portion) of the edge layer of the cleaning blade that comes into contact with the intermediate transfer belt can be determined in the same manner.

[0108] -composition- In this embodiment, a cleaning blade having a two-layer structure of an edge layer and a back layer is used, that is, a cleaning blade provided with an edge layer including a contact portion that contacts the intermediate transfer belt, and a back layer formed on the back side of the edge layer and made of a different material from the edge layer is used.

[0109] In the cleaning blade, the edge layer and the back layer are both made of a polyurethane resin.

[0110] Polyurethane resin The polyurethane resin is a polyurethane resin obtained by polymerizing at least a polyol component and a polyisocyanate component. If necessary, the polyurethane resin may be a polyurethane resin obtained by polymerizing a resin having a functional group capable of reacting with an isocyanate group of the polyisocyanate in addition to the polyol component.

[0111] The polyurethane resin preferably has a hard segment and a soft segment. The terms "hard segment" and "soft segment" refer to segments in which the material constituting the former is harder than the material constituting the latter, and the material constituting the latter is softer than the material constituting the former, in a polyurethane resin material. Examples of materials constituting the hard segment (hard segment materials) include low molecular weight polyol components among polyol components, resins having functional groups capable of reacting with isocyanate groups of polyisocyanates, etc. On the other hand, examples of materials constituting the soft segment (soft segment materials) include high molecular weight polyol components among polyol components.

[0112] Here, the average particle size of the hard segment aggregates is preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less. By setting the average particle size of the hard segment aggregates to 1 μm or more, the friction resistance on the surface of the contacting member is easily reduced, which stabilizes the blade behavior and makes it easier to suppress local wear. On the other hand, by setting the average particle size of the hard segment aggregates to 10 μm or less, the occurrence of chipping is easily suppressed.

[0113] The average particle size of the hard segment aggregates is measured as follows: Images were taken at a magnification of ×20 using a Pass BX51-P, and the images were binarized through image processing. The particle diameters (circle equivalent diameters) of the aggregates were measured at five points per cleaning blade (the particle diameters of five aggregates were measured at each point) for 20 cleaning blades, and the average particle diameter was calculated from a total of 500 particles. The images were binarized using the image processing software OLYMPUS Stream essentials (Olympus Corporation), and the hue / saturation / brightness thresholds were adjusted so that the crystalline parts and hard segment aggregates were black and the amorphous parts (corresponding to the soft segments) were white.

[0114] Polyol component The polyol component includes a high molecular weight polyol and a low molecular weight polyol.

[0115] The polymer polyol component is a polyol having a number average molecular weight of 500 or more (preferably 500 or more and 5000 or less). Examples of the polymer polyol component include well-known polyols such as polyester polyols obtained by dehydration condensation of low molecular weight polyols and dibasic acids, polycarbonate polyols obtained by reaction of low molecular weight polyols and alkyl carbonates, polycaprolactone polyols, and polyether polyols. Commercially available polymer polyols include, for example, PLACCEL 205 and PLACCEL 240 manufactured by Daicel Corporation.

[0116] Here, the number average molecular weight is a value measured by gel permeation chromatography (GPC). The same applies hereinafter.

[0117] These polymer polyols may be used alone or in combination of two or more kinds.

[0118] The polymerization ratio of the high molecular weight polyol component is preferably 30 mol % or more and 50 mol % or less, and more preferably 40 mol % or more and 50 mol % or less, based on the total polymerization components of the polyurethane resin.

[0119] The low molecular weight polyol component is a polyol having a molecular weight (number average molecular weight) of less than 500. The low molecular weight polyol is a material that functions as a chain extender and a crosslinking agent.

[0120] Examples of the low molecular weight polyol component include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosanediol. Among these, 1,4-butanediol is preferably used as the low molecular weight polyol component.

[0121] Examples of the low molecular weight polyol component include diols (2 functional), triols (3 functional), and tetraols (4 functional), which are well known as chain extenders and crosslinking agents. These polyols may be used alone or in combination of two or more kinds.

[0122] The polymerization ratio of the low molecular weight polyol component is preferably more than 50 mol% and 75 mol% or less, more preferably 52 mol% or more and 75 mol%, more preferably 55 mol% or more and 75 mol% or less, and even more preferably 55 mol% or more and 60 mol% or less, based on the total polymerization components of the polyurethane resin.

[0123] Polyisocyanate component Examples of the polyisocyanate component include 4,4'-diphenylmethane diisocyanate (MDI), 2,6-toluene diisocyanate (TDI), 1,6-hexanediisocyanate (TDI), isocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), and 3,3-dimethylbiphenyl-4,4'-diisocyanate (TODI).

[0124] As the polyisocyanate component, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), and hexamethylene diisocyanate (HDI) are more preferable.

[0125] These polyisocyanate components may be used alone or in combination of two or more kinds.

[0126] The polymerization ratio of the polyisocyanate component is preferably from 5 mol % to 25 mol %, and more preferably from 10 mol % to 20 mol %, based on the total polymerization components of the polyurethane resin.

[0127] Resins with functional groups that can react with isocyanate groups A resin having a functional group capable of reacting with an isocyanate group (hereinafter referred to as a "functional group-containing resin") is preferably a flexible resin, and from the viewpoint of flexibility, is more preferably an aliphatic resin having a linear structure. Specific examples of functional group-containing resins include acrylic resins containing two or more hydroxyl groups, polybutadiene resins containing two or more hydroxyl groups, and epoxy resins containing two or more epoxy groups.

[0128] An example of a commercially available acrylic resin containing two or more hydroxyl groups is Actflow (grades: UMB-2005B, UMB-2005P, UMB-2005, UME-2005, etc.) manufactured by Soken Chemical & Engineering Co., Ltd.

[0129] An example of a commercially available polybutadiene resin containing two or more hydroxyl groups is R-45HT manufactured by Idemitsu Kosan Co., Ltd.

[0130] The epoxy resin having two or more epoxy groups is not hard and brittle like conventional epoxy resins, but is more flexible and tough than conventional epoxy resins. For example, in terms of molecular structure, the epoxy resin preferably has a structure (flexible skeleton) in its main chain structure that can increase the mobility of the main chain, and examples of the flexible skeleton include an alkylene skeleton, a cycloalkane skeleton, and a polyoxyalkylene skeleton, and the polyoxyalkylene skeleton is particularly preferred. In terms of physical properties, epoxy resins with a lower viscosity relative to the molecular weight are preferred compared to conventional epoxy resins. Specifically, the weight average molecular weight is preferably within the range of 900±100, and the viscosity at 25°C is preferably within the range of 15000±5000 mPa·s, more preferably within the range of 15000±3000 mPa·s. Commercially available epoxy resins with these properties include, for example, EPLICON EXA-4850-150 manufactured by DIC.

[0131] The polymerization ratio of the functional group-containing resin is preferably set within a range that does not impair the properties of the cleaning blade.

[0132] -Method of manufacturing polyurethane resin The polyurethane resin is produced by a general polyurethane production method such as a prepolymer method or a one-shot method. The prepolymer method is suitable for this embodiment because it can produce polyurethane with excellent abrasion resistance and chipping resistance, but the production method is not limited. The cleaning blade is produced by forming the cleaning blade composition prepared by the above-mentioned method into a sheet shape by, for example, centrifugal molding or extrusion molding, and then cutting the sheet into a desired shape.

[0133] Examples of the catalyst used in the production of the polyurethane resin include amine compounds such as tertiary amines, quaternary ammonium salts, and organometallic compounds such as organotin compounds. Examples of the tertiary amine include trialkylamines such as triethylamine, tetraalkyldiamines such as N,N,N',N'-tetramethyl-1,3-butanediamine, aminoalcohols such as dimethylethanolamine, ethoxylated amines, ethoxylated diamines, ester amines such as bis(diethylethanolamine) adipate, triethylenediamine (TEDA), cyclohexylamine derivatives such as N,N-dimethylcyclohexylamine, morpholine derivatives such as N-methylmorpholine and N-(2-hydroxypropyl)-dimethylmorpholine, piperazine derivatives such as N,N'-diethyl-2-methylpiperazine and N,N'-bis-(2-hydroxypropyl)-2-methylpiperazine, and the like.

[0134] Examples of quaternary ammonium salts include 2-hydroxypropyltrimethylammonium octylate, 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) octylate, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) octylate, DBU-oleate, DBU-p-toluenesulfonate, DBU-formate, and 2-hydroxypropyltrimethylammonium formate.

[0135] Examples of the organotin compound include dialkyltin compounds such as dibutyltin dilaurate and dibutyltin di(2-ethylhexoate), stannous 2-ethylcaproate, and stannous oleate.

[0136] Among these catalysts, the tertiary ammonium salt triethylenediamine (TEDA) is used in terms of hydrolysis resistance, and quaternary ammonium salts are preferred in terms of processability. Among the quaternary ammonium salts, 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) octylate, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) octylate, and DBU formate are preferred, as they have high reactivity.

[0137] The content of the catalyst is preferably in the range of 0.0005% by mass to 0.03% by mass, and particularly preferably in the range of 0.001% by mass to 0.01% by mass, of the entire polyurethane resin constituting the contact member. These may be used alone or in combination of two or more.

[0138] - Fabrication of a two-layer cleaning blade The edge layer and the back layer are integrally molded by centrifugal molding. First, the molten material of the back layer is poured into a centrifugal molding drum, which is then rotated. This causes the material of the back layer to spread evenly over the inner circumferential surface of the centrifugal molding drum, and gradually solidifies. Then, before the material of the back layer is completely solidified (while the material still has tackiness), the molten material of the edge layer is poured into the centrifugal molding drum, which is then rotated to solidify the material. The solidified material is then removed from the centrifugal molding drum, and the cleaning blade is cut out. In addition, a cleaning blade having a two-layer structure of an edge layer and a back layer can also be produced by producing the edge layer and the back layer separately by the above-mentioned method for producing a polyurethane resin, and then laminating the obtained edge layer and back layer together. In order to make the edge layer and the back surface layer different in hardness, the polyurethane resin material may be changed, for example, by changing the ratio of the hard segment to the soft segment.

[0139] -Contact area modification treatment In this embodiment, in order to set the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the edge layer of the cleaning blade that contacts the intermediate transfer belt to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) within the above-mentioned range, it is preferable to have a modified layer that has been surface-modified by penetrating at least one of F element and Si element into the contact portion of the edge layer of the obtained cleaning blade.

[0140] The modified layer is a layer formed by impregnating the contact portion of the cleaning blade with a surface treatment liquid containing an isocyanate compound, a specific polymer having at least one of an F element and an Si element, and an organic solvent, and then hardening the surface treatment liquid (i.e., the isocyanate compound and the specific polymer). The modified layer is formed integrally with the surface layer of the contact portion so as to become gradually sparser from the surface toward the inside.

[0141] Examples of the isocyanate compound include 2,6-tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), paraphenylene diisocyanate (PPDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethyldiphenyl-4,4'-diisocyanate (TODI), as well as polymers and modified products thereof. Examples of modified products of the isocyanate compound include urethane prepolymers in which an isocyanate compound is prepolymerized together with a polyol.

[0142] The specific polymer is preferably a compound that is soluble in a specific solvent and reacts with an isocyanate compound to form a chemical bond. Examples of acrylic polymers having siloxane bonds include block copolymers of (meth)acrylic acid esters and (meth)acrylic acid siloxane esters, and derivatives thereof. Note that "(meth)acrylic" means either acrylic or methacrylic, or both. Examples of acrylic polymers having fluorine atoms include block copolymers of (meth)acrylic acid esters and fluorinated alkyl (meth)acrylates, and derivatives thereof. The cleaning blade preferably contains a polymer having a siloxane bond (a silicone-based polymer) in the portion that comes into contact with the transfer belt. From the viewpoint of solubility in organic solvents, the specific polymer is preferably a compound having a hydroxyl group, an alkyl group, or a carboxyl group.

[0143] The following methods can be used to confirm that the cleaning blade contains a specific polymer in the surface layer of the contact area, and that the surface layer contains a specific polymer that is an acrylic polymer. Specifically, the confirmation is performed by estimating the structure and analyzing the composition of the surface layer material of the contact area of ​​the cleaning blade using an analytical method such as Fourier transform infrared spectrophotometer (FTIR) or X-ray photoelectron spectroscopy (XPS).

[0144] The content of the specific polymer in the surface treatment liquid is, for example, 8 parts by mass or more and 13 parts by mass or less, preferably 9 parts by mass or more and 13 parts by mass or less, and more preferably 10 parts by mass or more and 13 parts by mass or less, relative to 100 parts by mass of the isocyanate compound.

[0145] The organic solvent is preferably one that dissolves the specific polymer and is compatible with the isocyanate compound, and specific examples thereof include ethyl acetate, methyl ethyl ketone (MEK), toluene, acetone, cyclohexanone, etc. In addition, reactive diluents such as 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, and trimethylolpropane triacrylate may also be used as the organic solvent.

[0146] The modified layer is formed, for example, by impregnating and applying the above-mentioned surface treatment liquid onto at least the contact portion of the cleaning blade, drying to remove the organic solvent, and then heating to form a hardened layer. The impregnation coating method is not particularly limited, and examples thereof include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, curtain coating, etc. When the impregnation coating method is the dip coating method, the immersion time is, for example, in the range of 10 seconds or more and 60 seconds or less. Drying conditions after the impregnation coating include, for example, a temperature of 20° C. to 30° C. and a time of 1 to 10 minutes, and heat treatment conditions include, for example, a temperature of 50° C. to 80° C. and a time of 60 to 90 minutes.

[0147] Pressing pressure The pressing pressure NF (Normal Force) with which the cleaning blade is pressed against the intermediate transfer belt is preferably 1.5 gf / mm to 3.5 gf / mm, more preferably 2.0 gf / mm to 3.2 gf / mm. When the pressing pressure NF is 1.5 gf / mm or more, the occurrence of staple marks in the image is further suppressed, and when the pressing pressure NF is 3.5 gf / mm or less, the occurrence of toner filming on the surface of the intermediate transfer belt is further suppressed.

[0148] Here, the pressing pressure NF of the cleaning blade is calculated by the following formula. Formula: Pressing pressure NF = k × d In the formula, k is the spring constant specific to the cleaning blade, and d is the amount of penetration of the cleaning blade into the intermediate transfer belt (see FIG. 2). The spring constant k specific to the cleaning blade is obtained by applying a displacement to the cleaning blade 12 and measuring the load with a load cell. The amount of penetration d of the cleaning blade into the intermediate transfer belt is calculated by fixing the cleaning blade 12 to a supporting member and calculating the amount of displacement of the cleaning blade when the cleaning blade is brought into contact with the intermediate transfer belt. In FIG. 2, BE denotes an intermediate transfer belt, CB denotes a cleaning blade, and CBS denotes a support member for supporting the cleaning blade.

[0149] The depth d of the cleaning blade penetrating into the intermediate transfer belt is preferably 0 mm or more and 10 mm or less, and more preferably 0.01 mm or more and 5 mm or less.

[0150] (Intermediate transfer belt and transfer device) -Layer structure of intermediate transfer belt- The intermediate transfer belt may be, for example, a single layer of a polyimide resin layer, or a laminate having a polyimide resin layer as the outermost layer. The intermediate transfer belt preferably has an outer peripheral surface made of a polyimide resin layer.

[0151] When the intermediate transfer belt is composed of a laminate having a polyimide-based resin layer as the outermost layer, an intermediate transfer belt having a polyimide-based resin layer provided on a resin substrate layer is used. An intermediate layer (such as an elastic layer) may be provided between the substrate layer and the polyimide-based resin layer. The resin substrate layer and the intermediate layer (elastic layer, etc.) may be any well-known layer that is used in an intermediate transfer belt.

[0152] [Polyimide resin layer configuration] The polyimide-based resin layer contains, for example, a polyimide-based resin and conductive carbon particles. The polyimide-based resin layer preferably contains a release agent. The polyimide-based resin layer may contain other well-known components as necessary.

[0153] Here, the polyimide-based resin layer is a layer that contains polyimide-based resin in the largest amount by mass among the resin layer constituent components.

[0154] -Polyimide resin- The polyimide resin means a resin containing a structural unit having an imide bond. Examples of the polyimide resin include polyimide resin, polyamideimide resin, and polyetherimide resin. Among these, from the viewpoint of cleaning maintenance, the polyimide resin is preferably a polyimide resin or a polyamideimide resin, and more preferably a polyimide resin.

[0155] Examples of polyimide resins include imidized products of polyamic acids (precursors of polyimide resins), which are polymers of tetracarboxylic dianhydrides and diamine compounds. An example of the polyimide resin is a resin having a structural unit represented by the following general formula (I).

[0156] [ka]

[0157] In general formula (I), R 1 represents a tetravalent organic group, R 2 represents a divalent organic group. R 1 Examples of the tetravalent organic group represented by the formula (1) include an aromatic group, an aliphatic group, a cyclic aliphatic group, a group in which an aromatic group and an aliphatic group are combined, and groups in which these groups are substituted. Specific examples of the tetravalent organic group include residues of tetracarboxylic dianhydrides, which will be described later. R 2 Examples of the divalent organic group represented by the formula (1) include an aromatic group, an aliphatic group, a cyclic aliphatic group, a group in which an aromatic group and an aliphatic group are combined, and a group in which these groups are substituted. Specific examples of the divalent organic group include residues of diamine compounds described below.

[0158] Specific examples of tetracarboxylic dianhydrides used as raw materials for polyimide resins include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and the like. Examples of the dianhydride include tetracarboxylic acid dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)sulfonic acid dianhydride, perylene-3,4,9,10-tetracarboxylic acid dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, and ethylene tetracarboxylic acid dianhydride.

[0159] Specific examples of diamine compounds used as raw materials for polyimide resins include 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,3'-dichlorobenzidine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 1,5-diaminonaphthalene, m-phenylenediamine, p-phenylenediamine, 3,3'-dimethyl 4,4'-biphenyldiamine, benzidine, and 3,3'-dimethyl Benzidine, 3,3'-dimethoxybenzidine, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenylpropane, 2,4-bis(β-amino tert-butyl)toluene, bis(p-β-amino-tert-butylphenyl)ether, bis(p-β-methyl-δ-aminophenyl)benzene, bis-p-(1,1-dimethyl-5-amino-pentyl)benzene, 1-isopropyl-2,4-m-phenylenediamine, m-xylylenediamine, p-xylylenediamine, di(p -aminocyclohexyl)methane, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, diaminopropyltetramethylene, 3-methylheptamethylenediamine, 4,4-dimethylheptamethylenediamine, 2,11-diaminododecane, 1,2-bis-3-aminopropoxyethane, 2,2-dimethylpropylenediamine, 3-methoxyhexamethylenediamine, 2,5-dimethylheptamethylenediamine, Examples include 3-methylheptamethylenediamine, 5-methylnonamethylenediamine, 2,17-diaminoeicosadecane, 1,4-diaminocyclohexane, 1,10-diamino-1,10-dimethyldecane, 12-diaminooctadecane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, piperazine, H2N(CH2)3O(CH2)2O(CH2)NH2, H2N(CH2)3S(CH2)3NH2, and H2N(CH2)3N(CH3)2(CH2)3NH2.

[0160] The polyamide-imide resin may be a resin having an imide bond and an amide bond in the repeating unit. More specifically, the polyamide-imide resin may be a polymer of a trivalent carboxylic acid compound (also called tricarboxylic acid) having an acid anhydride group, and a diisocyanate compound or a diamine compound.

[0161] As the tricarboxylic acid, trimellitic anhydride and its derivatives are preferable. In addition to the tricarboxylic acid, tetracarboxylic dianhydride, aliphatic dicarboxylic acid, aromatic dicarboxylic acid, etc. may be used in combination.

[0162] Examples of the diisocyanate compound include 3,3'-dimethylbiphenyl-4,4'-diisocyanate, 2,2'-dimethylbiphenyl-4,4'-diisocyanate, biphenyl-4,4'-diisocyanate, biphenyl-3,3'-diisocyanate, biphenyl-3,4'-diisocyanate, 3,3'-diethylbiphenyl-4,4'-diisocyanate, 2,2'-diethylbiphenyl-4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, 2,2'-dimethoxybiphenyl-4,4'-diisocyanate, naphthalene-1,5-diisocyanate, and naphthalene-2,6-diisocyanate. The diamine compound may be a compound having a structure similar to that of the above-mentioned isocyanate, but having an amino group instead of the isocyanato group.

[0163] The content of the polyimide resin in the polyimide resin layer affects the mechanical strength and volume resistance. From the viewpoint of adjusting the ratio, etc., it is preferably from 60% by mass to 95% by mass, more preferably from 70% by mass to 95% by mass, and even more preferably from 75% by mass to 90% by mass.

[0164] -Conductive carbon particles- An example of the conductive carbon particles is carbon black. Examples of carbon black include ketjen black, oil furnace black, channel black, acetylene black, etc. As the carbon black, surface-treated carbon black (hereinafter also referred to as "surface-treated carbon black") may be used. Surface-treated carbon black can be obtained by imparting, for example, a carboxy group, a quinone group, a lactone group, a hydroxy group, etc. to its surface. Examples of the surface treatment method include an air oxidation method in which the carbon black is reacted by contacting with air in a high-temperature atmosphere, a method in which the carbon black is reacted with nitrogen oxides or ozone at room temperature (e.g., 22°C), and a method in which the carbon black is oxidized with air in a high-temperature atmosphere and then oxidized with ozone at a low temperature.

[0165] The average particle size of the conductive carbon particles is preferably 2 nm to 40 nm, more preferably 8 nm to 20 nm, and even more preferably 10 nm to 15 nm, from the viewpoints of dispersibility, mechanical strength, volume resistivity, film-forming properties, and the like.

[0166] The average particle size of the conductive carbon particles is measured by the following method. First, a measurement sample with a thickness of 100 nm is taken from the polyimide resin layer using a microtome, and this measurement sample is observed using a TEM (transmission electron microscope).Then, the diameter of a circle equal to the projected area of ​​each of 50 conductive carbon particles (i.e., the equivalent circle diameter) is taken as the particle diameter, and the average of these is taken as the average particle diameter.

[0167] The content of the conductive carbon particles is preferably 10% by mass or more and 50% by mass or less with respect to the polyimide-based resin layer, from the viewpoints of mechanical strength and volume resistivity.

[0168] -Other ingredients- Examples of other components include conductive agents other than conductive carbon particles, fillers for improving mechanical strength, antioxidants for preventing thermal deterioration of the belt, surfactants for improving fluidity, heat-resistant anti-aging agents, and release agents. When other components are contained, the content of the other components is preferably more than 0 mass% and not more than 10 mass%, more preferably more than 0 mass% and not more than 5 mass%, and even more preferably more than 0 mass% and not more than 1 mass%, relative to the polyimide resin layer.

[0169] Thickness of polyimide resin layer When the intermediate transfer belt is composed of a single layer of a polyimide resin layer, the thickness of the polyimide resin layer is preferably 60 μm or more and 120 μm or less, and more preferably 80 μm or more and 120 μm or less, from the viewpoint of mechanical strength. When the intermediate transfer belt is formed of a laminate having a polyimide-based resin layer as the outermost layer, the thickness of the polyimide-based resin layer is preferably 1 μm or more and 60 μm or less, and more preferably 3 μm or more and 60 μm or less, from the viewpoints of manufacturability and suppression of discharge.

[0170] The thickness of the polyimide-based resin layer is measured as follows. That is, a cross section of the polyimide resin layer in the thickness direction is observed with an optical microscope or a scanning electron microscope, the thickness of the layer to be measured is measured at 10 points, and the average value is taken as the thickness.

[0171] -Volume resistivity of intermediate transfer belt From the viewpoint of transferability, the common logarithm of the volume resistivity of the intermediate transfer belt when a voltage of 500 V is applied for 10 seconds is preferably 9.0 (log Ω·cm) or more and 13.5 (log Ω·cm) or less, more preferably 9.5 (log Ω·cm) or more and 13.2 (log Ω·cm) or less, and particularly preferably 10.0 (log Ω·cm) or more and 12.5 (log Ω·cm) or less. The volume resistivity of the intermediate transfer belt when a voltage of 500 V is applied for 10 seconds is measured by the following method. A microcurrent meter (Advantest R8430A) is used as the resistance measuring device, and a UR probe (Mitsubishi Chemical Analytech Co., Ltd.) is used as the probe to measure the volume resistivity (log Ω cm) at 6 equally spaced points around the periphery of the intermediate transfer belt, and 3 points at the center and both ends in the width direction, for a total of 18 points, at a voltage of 500 V, application time of 10 seconds, and pressure of 1 kgf, and the average value is calculated. The measurements are also performed in an environment with a temperature of 22°C and a humidity of 55% RH.

[0172] Surface resistivity of intermediate transfer belt From the viewpoint of transferability to textured paper, the common logarithm of the surface resistivity when a voltage of 500 V is applied to the outer peripheral surface of the intermediate transfer belt for 10 seconds is preferably 10.0 (log Ω / suq.) or more and 15.0 (log Ω / suq.) or less, more preferably 10.5 (log Ω / suq.) or more and 14.0 (log Ω / suq.) or less, and particularly preferably 11.0 (log Ω / suq.) or more and 13.5 (log Ω / suq.) or less. The unit of surface resistivity, logΩ / suq., is a logarithmic value of the resistance per unit area, and is also expressed as log(Ω / suq.), logΩ / suquare, logΩ / □, etc. The surface resistivity when a voltage of 500 V is applied to the outer peripheral surface of the intermediate transfer belt for 10 seconds is measured by the following method. A microammeter (R8430A manufactured by Advantest) is used as the resistance measuring device, and a UR probe (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) is used as the probe to measure the surface resistivity (logΩ / suq.) of the outer peripheral surface of the endless belt at 6 equally spaced points in the circumferential direction of the outer peripheral surface of the intermediate transfer belt, and 3 points in the center and both ends in the width direction, for a total of 18 points, at a voltage of 500V, an application time of 10 seconds, and a pressure of 1kgf, and the average value is calculated. The measurements are also performed in an environment with a temperature of 22°C and a humidity of 55%RH.

[0173] - Primary transfer device - In the primary transfer device, a primary transfer member is disposed opposite to an image carrier with an intermediate transfer belt interposed therebetween. In the primary transfer device, a voltage of a polarity opposite to the charge polarity of the toner is applied to the intermediate transfer belt by the primary transfer member, whereby the toner image is primarily transferred onto the outer peripheral surface of the intermediate transfer belt.

[0174] -Secondary transfer device- In the secondary transfer device, the secondary transfer member is disposed on the toner image carrying side of the intermediate transfer belt. The secondary transfer device includes, for example, a backing member disposed on the opposite side of the intermediate transfer belt from the toner image carrying side together with the secondary transfer member. In the secondary transfer device, the intermediate transfer belt and the recording medium are sandwiched between the secondary transfer member and the backing member to form a transfer electric field, whereby the toner image on the intermediate transfer belt is secondarily transferred to the recording medium. The secondary transfer member may be a secondary transfer roll or a secondary transfer belt. The backing member may be, for example, a backing roll.

[0175] -Other configurations of the transfer device- The present embodiment may be a transfer device that transfers a toner image onto a surface of a recording medium via multiple intermediate transfer belts. In other words, the transfer device may be, for example, a transfer device that primarily transfers a toner image from an image carrier to a first intermediate transfer belt, secondarily transfers the toner image from the first intermediate transfer belt to a second intermediate transfer belt, and then tertiarily transfers the toner image from the second intermediate transfer belt to a recording medium. A transfer device applies the intermediate transfer belt according to the present embodiment to at least one of a plurality of intermediate transfer belts.

[0176] (Configuration of Image Forming Apparatus) The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for accommodating an electrostatic image developer containing a toner having toner particles and for developing the electrostatic image formed on the surface of the image carrier by the electrostatic image developer as a toner image, an intermediate transfer belt having a toner image transferred onto its outer circumferential surface, a primary transfer means having a primary transfer member for primarily transferring the toner image formed on the surface of the image carrier onto the outer circumferential surface of the intermediate transfer belt, a secondary transfer means having a secondary transfer member for secondarily transferring the toner image primarily transferred onto the outer circumferential surface of the intermediate transfer belt onto the surface of a recording medium, and a cleaning device having a cleaning blade for contacting and cleaning the outer circumferential surface of the intermediate transfer belt.

[0177] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as an apparatus equipped with a fixing means for fixing a toner image transferred onto the surface of a recording medium; an apparatus equipped with a cleaning device for cleaning the surface of an image holder before charging after the toner image is transferred; an apparatus equipped with a static elimination device for irradiating the surface of an image holder with static elimination light before charging after the toner image is transferred; and an apparatus equipped with an image holder heating member for increasing the temperature of the image holder and reducing the relative temperature.

[0178] The image forming apparatus according to the present embodiment may be either a dry development type image forming apparatus or a wet development type image forming apparatus (a development type using a liquid developer).

[0179] In the image forming apparatus according to the present embodiment, for example, the portion including the image carrier may be a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a toner image forming device and a transfer device is preferably used.

[0180] (Image forming method) The image forming method according to this embodiment includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using an electrostatic image developer containing a toner having toner particles, a primary transfer step of primarily transferring the toner image formed on the surface of the image carrier onto the outer peripheral surface of an intermediate transfer belt, a secondary transfer step of secondarily transferring the toner image primarily transferred onto the outer peripheral surface of the intermediate transfer belt onto the surface of a recording medium, and a cleaning step of contacting the outer peripheral surface of the intermediate transfer belt with a cleaning blade to clean it. The toner particles have a releasing agent present within 800 nm from the surface that accounts for 70% or more of the releasing agent in the entire toner particle, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less. The cleaning blade has a two-layer structure consisting of an edge layer and a back layer, and the edge layer and the back layer are made of polyurethane resin. The cleaning blade has a ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer of 0.84 to 0.93, and the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.

[0181] Hereinafter, an example of an image forming apparatus and an image forming method according to the present embodiment will be described with reference to the drawings. However, the image forming apparatus and the image forming method according to the present embodiment are not limited to this. Note that the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0182] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment.

[0183] 1, the image forming apparatus 100 according to the present embodiment is, for example, an intermediate transfer type image forming apparatus generally called a tandem type, and includes a plurality of image forming units 1Y, 1M, 1C, and 1K (an example of a toner image forming apparatus) in which toner images of each color component are formed by an electrophotographic method, a primary transfer section 10 that sequentially transfers (primary transfer) the toner images of each color component formed by each image forming unit 1Y, 1M, 1C, and 1K onto an intermediate transfer belt 15, a secondary transfer section 20 that collectively transfers (secondary transfer) the superimposed toner images transferred onto the intermediate transfer belt 15 onto a recording medium, paper K, and a fixing device 60 that fixes the secondary transferred image onto the paper K. The image forming apparatus 100 also has a control section 40 that controls the operation of each device (each section).

[0184] Each of the image forming units 1Y, 1M, 1C, and 1K of the image forming apparatus 100 includes a photoconductor 11 (an example of an image carrier) that rotates in the direction of arrow A and carries a toner image formed on its surface.

[0185] Around the photoconductor 11, there is provided a charger 12 as an example of a charging means for charging the photoconductor 11, and there is provided a laser exposure device 13 (the exposure beam is indicated by the symbol Bm in the figure) as an example of a latent image forming means for writing an electrostatic latent image on the photoconductor 11.

[0186] In addition, around the photoconductor 11, there is provided a developing device 14 as an example of a developing means, which contains each color component toner and makes the electrostatic latent image on the photoconductor 11 visible using the toner, and there is provided a primary transfer roll 16 which transfers each color component toner image formed on the photoconductor 11 to an intermediate transfer belt 15 at the primary transfer section 10.

[0187] Furthermore, a photoreceptor cleaner 17 that removes residual toner on the photoreceptor 11 is provided around the photoreceptor 11, and electrophotographic devices including a charger 12, a laser exposure device 13, a developer 14, a primary transfer roll 16, and the photoreceptor cleaner 17 are sequentially arranged along the rotation direction of the photoreceptor 11. These image forming units 1Y, 1M, 1C, and 1K are arranged in a substantially linear fashion in the order of yellow (Y), magenta (M), cyan (C), and black (K) from the upstream side of the intermediate transfer belt 15.

[0188] 1 at a speed suited to the purpose. These rolls include a drive roll 31 that is driven by a motor (not shown) with excellent constant speed performance to rotate the intermediate transfer belt 15, a support roll 32 that supports the intermediate transfer belt 15 that extends in a substantially straight line along the arrangement direction of the photoconductors 11, a tension applying roll 33 that applies tension to the intermediate transfer belt 15 and functions as a correction roll that prevents the intermediate transfer belt 15 from meandering, a back roll 25 provided in the secondary transfer unit 20, and a roller 36 that is provided in the intermediate transfer unit 20. The intermediate transfer belt 15 has a cleaning back roll 34 disposed opposite an intermediate transfer belt cleaning blade 35 for scraping off residual toner on the intermediate transfer belt 15 .

[0189] The primary transfer section 10 is composed of a primary transfer roll 16 arranged opposite the photoconductor 11 with the intermediate transfer belt 15 sandwiched therebetween. The primary transfer roll 16 is arranged in pressure contact with the photoconductor 11 with the intermediate transfer belt 15 sandwiched therebetween, and a voltage (primary transfer bias) of the opposite polarity to the charge polarity of the toner (negative polarity; the same applies below) is applied to the primary transfer roll 16. As a result, the toner images on the photoconductors 11 are electrostatically attracted to the intermediate transfer belt 15 in sequence, and superimposed toner images are formed on the intermediate transfer belt 15.

[0190] The secondary transfer unit 20 includes a back roll 25 and a secondary transfer roll 22 that is disposed on the toner image bearing surface side of the intermediate transfer belt 15 .

[0191] The back roll 25 has a surface resistivity of 1×10 7 Ω / □ or more 1×10 10 The hardness is set to, for example, 70° (Asker C: manufactured by Kobunshi Keiki Co., Ltd., the same applies below.) The back roll 25 is disposed on the back side of the intermediate transfer belt 15 to constitute an opposing electrode of the secondary transfer roll 22, and is in contact with a metallic power supply roll 26 to which a secondary transfer bias is stably applied.

[0192] On the other hand, the secondary transfer roll 22 has a volume resistivity of 10 7.5 Ωcm or more 10 8.5 The secondary transfer roll 22 is a cylindrical roll of Ωcm or less. The secondary transfer roll 22 is arranged in pressure contact with the back roll 25 with the intermediate transfer belt 15 sandwiched therebetween, and the secondary transfer roll 22 is further grounded to form a secondary transfer bias between the secondary transfer roll 22 and the back roll 25, and performs a second transfer of the toner image onto the paper K transported to the secondary transfer unit 20.

[0193] In addition, an intermediate transfer belt cleaning blade 35 is provided on the downstream side of the secondary transfer section 20 of the intermediate transfer belt 15 in a manner that allows it to freely come into contact with and separate from the intermediate transfer belt 15. The intermediate transfer belt cleaning blade 35 removes residual toner and paper dust from the intermediate transfer belt 15 after the secondary transfer and cleans the outer peripheral surface of the intermediate transfer belt 15. Further, a secondary transfer roll cleaning member 22A is provided downstream of the secondary transfer section 20 of the secondary transfer roll 22 to remove residual toner and paper powder on the secondary transfer roll 22 after secondary transfer and clean the outer circumferential surface of the intermediate transfer belt 15. The secondary transfer roll cleaning member 22A is exemplified by a cleaning blade, but may also be a cleaning roll.

[0194] The intermediate transfer belt 15, the primary transfer roll 16, the secondary transfer roll 22, and the intermediate transfer belt cleaning member 35 correspond to an example of a transfer device. Here, the image forming apparatus 100 may be configured to include a secondary transfer belt (an example of a secondary transfer member) instead of the secondary transfer roll 22.

[0195] Meanwhile, a reference sensor (home position sensor) 42 is provided upstream of the yellow image forming unit 1Y to generate a reference signal that serves as a reference for timing image formation in each of the image forming units 1Y, 1M, 1C, and 1K. An image density sensor 43 for adjusting image quality is provided downstream of the black image forming unit 1K. This reference sensor 42 generates a reference signal by recognizing a mark provided on the back side of the intermediate transfer belt 15, and each of the image forming units 1Y, 1M, 1C, and 1K is configured to start image formation in response to an instruction from the control unit 40 based on the recognition of this reference signal.

[0196] Furthermore, in the image forming apparatus according to the present embodiment, as a conveying means for conveying the paper K, a paper storage section 50 for storing the paper K, a paper storage section 50 for storing the paper K, and a paper storage section 50 for storing the paper K stacked in the paper storage section 50 according to a predetermined timing are provided. The transfer device 20 includes a paper feed roll 51 which takes out the paper K in a timing and transports it, a transport roll 52 which transports the paper K fed by the paper feed roll 51, a transport guide 53 which sends the paper K transported by the transport roll 52 to the secondary transfer section 20, a transport belt 55 which transports the paper K transported after the secondary transfer by the secondary transfer roll 22 to the fixing device 60, and a fixing entrance guide 56 which guides the paper K to the fixing device 60.

[0197] Next, a basic image forming process, that is, an image forming method, of the image forming apparatus according to this embodiment will be described. In the image forming apparatus of this embodiment, image data output from an image reading device (not shown) or a personal computer (PC) (not shown), etc., is subjected to image processing by an image processing device (not shown), and then image formation is performed by image forming units 1Y, 1M, 1C, and 1K.

[0198] The image processing device performs image processing on the input reflectance data, such as shading correction, positional deviation correction, brightness / color space conversion, gamma correction, and various image editing such as frame erasure, color editing, and movement editing. The image data that has undergone image processing is converted into color material gradation data of four colors, Y, M, C, and K, and is output to the laser exposure device 13.

[0199] In the laser exposure device 13, an exposure beam Bm emitted from, for example, a semiconductor laser is irradiated onto the photoconductor 11 of each of the image forming units 1Y, 1M, 1C, and 1K in accordance with the input color material gradation data. In each of the photoconductors 11 of the image forming units 1Y, 1M, 1C, and 1K, the surface is charged by the charger 12, and then the surface is scanned and exposed by the laser exposure device 13 to form an electrostatic latent image. The formed electrostatic latent image is developed into a toner image of each color of Y, M, C, and K by each of the image forming units 1Y, 1M, 1C, and 1K.

[0200] The toner images formed on the photoconductors 11 of the image forming units 1Y, 1M, 1C, and 1K are transferred onto the intermediate transfer belt 15 in the primary transfer section 10 where each photoconductor 11 comes into contact with the intermediate transfer belt 15. More specifically, in the primary transfer section 10, a voltage (primary transfer bias) of the opposite polarity to the charging polarity (negative polarity) of the toner is applied to the base material of the intermediate transfer belt 15 by the primary transfer roll 16, and the toner images are sequentially superimposed on the outer circumferential surface of the intermediate transfer belt 15 to perform the primary transfer.

[0201] After the toner images are sequentially primarily transferred onto the outer peripheral surface of the intermediate transfer belt 15, the intermediate transfer belt 15 moves to transport the toner images to the secondary transfer unit 20. When the toner images are transported to the secondary transfer unit 20, the transport means rotates the paper feed roll 51 in accordance with the timing at which the toner images are transported to the secondary transfer unit 20, and paper K of the desired size is supplied from the paper storage unit 50. The paper K supplied by the paper feed roll 51 is transported by the transport roll 52 and reaches the secondary transfer unit 20 via the transport guide 53. Before reaching the secondary transfer unit 20, the paper K is temporarily stopped, and a positioning roll (not shown) rotates in accordance with the movement timing of the intermediate transfer belt 15 on which the toner images are held, thereby aligning the position of the paper K with the position of the toner image.

[0202] In the secondary transfer section 20, the secondary transfer roll 22 is pressed against the back roll 25 via the intermediate transfer belt 15. At this time, the paper K, which has been transported in time, is sandwiched between the intermediate transfer belt 15 and the secondary transfer roll 22. At this time, when a voltage (secondary transfer bias) of the same polarity as the charging polarity (negative polarity) of the toner is applied from the power supply roll 26, a transfer electric field is formed between the secondary transfer roll 22 and the back roll 25. Then, the unfixed toner images held on the intermediate transfer belt 15 are electrostatically transferred collectively onto the paper K in the secondary transfer section 20, which is pressed by the secondary transfer roll 22 and the back roll 25.

[0203] Then, the paper K onto which the toner image has been electrostatically transferred is transferred to the intermediate transfer belt by the secondary transfer roll 22. The paper K is transported in that state after being peeled off from the roller 15, and is transported to a transport belt 55 provided downstream of the secondary transfer roller 22 in the paper transport direction. The transport belt 55 transports the paper K to the fixing device 60 at an optimal transport speed for the fixing device 60. The unfixed toner image on the paper K transported to the fixing device 60 is fixed onto the paper K by being subjected to a fixing process using heat and pressure by the fixing device 60. The paper K on which the fixed image has been formed is then transported to a discharged paper storage section (not shown) provided in the discharge section of the image forming apparatus.

[0204] On the other hand, after the transfer to the paper K is completed, the residual toner remaining on the intermediate transfer belt 15 is transported to the intermediate transfer belt cleaning blade 35 as the intermediate transfer belt 15 rotates, and is removed from the intermediate transfer belt 15 by the intermediate transfer belt cleaning blade 35.

[0205] Although the present embodiment has been described above, the present invention is not limited to the above embodiment, and various modifications, changes, and improvements are possible. EXAMPLES

[0206] Hereinafter, examples of the present disclosure will be described, but the present disclosure is not limited to the following examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.

[0207] Example 1 <Preparation of electrostatic image developer> -Preparation of amorphous polyester resin dispersion- (Preparation of polyester resin dispersion (APE1)) Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 parts by mole Bisphenol A propylene oxide adduct: 95 parts by mole The above materials were charged into a 5-liter flask equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column, and the temperature was raised to 210°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature was raised to 230°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at that temperature for 1 hour, after which the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized.

[0208] 40 parts of ethyl acetate and 25 parts of 2-butanol were added to a vessel equipped with a temperature control means and a nitrogen replacement means to prepare a mixed solvent, after which 100 parts of polyester resin were gradually added and dissolved, and a 10% by mass aqueous ammonia solution (equivalent to 3 times the molar amount of the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the container was replaced with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped at a rate of 2 parts / min while stirring the mixture, to perform emulsification. After the dropwise addition was completed, the emulsion was returned to room temperature (20°C to 25°C), and dry nitrogen was bubbled for 48 hours while stirring to reduce ethyl acetate and 2-butanol to 1,000 ppm or less, and a resin particle dispersion in which resin particles having a volume average particle size of 200 nm were dispersed was obtained. Ion-exchanged water was added to the resin particle dispersion to adjust the solid content to 20 mass%, to obtain a polyester resin particle dispersion (APE1).

[0209] -Preparation of colorant particle dispersion- (Preparation of Colorant Particle Dispersion (Black Pigment Dispersion)) Carbon black (Cabot, Regal 330): 250 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen SC): 33 parts (60% active ingredient, 8% colorant) -Ion-exchanged water: 750 parts 280 parts of ion-exchanged water and 33 parts of anionic surfactant were placed in a stainless steel container of a size such that the height of the liquid surface would be about 1 / 3 of the height of the container when all of the above components were added, and after the surfactant was sufficiently dissolved, all of the solid solution pigment was added and stirred with a stirrer until there was no unwetted pigment, and the mixture was sufficiently defoamed. After defoaming, the remaining ion-exchanged water was added, and the mixture was dispersed for 10 minutes at 5000 rpm using a homogenizer (IKA Ultra Turrax T50), and then defoamed by stirring with a stirrer for 1 day and night. After defoaming, the mixture was dispersed again for 10 minutes at 6000 rpm using a homogenizer, and then defoamed by stirring with a stirrer for 1 day and night. Subsequently, the dispersion was dispersed at a pressure of 240 MPa using a high-pressure impact disperser Ultimizer (Sugino Machine Co., Ltd., HJP30006). Dispersion was performed for 25 passes, calculated from the total amount charged and the processing capacity of the device. The resulting dispersion was left to stand for 72 hours to remove the precipitate, and ion-exchanged water was added to adjust the solid content to 15%, to obtain a colorant particle dispersion. The volume average particle size D50 of the particles in this colorant particle dispersion was 135 nm.

[0210] -Preparation of release agent dispersion- (Preparation of release agent dispersion (WAX1)) Paraffin wax (HNP9 made by Nippon Seiro, melting temperature 75℃): 270 parts Anionic surfactant (Dai-ichi Kogyo Seiyaku Co., Ltd., Neogen RK, active ingredient amount: 60%): 13.5 parts (as an active ingredient, 3.0% relative to the release agent) Ion-exchanged water: 21.6 parts The above components were mixed and the release agent was dissolved in a pressure discharge homogenizer (Gaulin homogenizer, manufactured by Gaulin Co., Ltd.) at an internal liquid temperature of 120°C. The mixture was then dispersed at a dispersion pressure of 5 MPa for 120 minutes, then at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion (WAX1). The volume average particle size D50 of the particles in this release agent dispersion (WAX1) was 225 nm. Ion-exchanged water was then added to adjust the solid content to 20.0%.

[0211] -Preparation of mixed particle dispersion- (Preparation of mixed particle dispersion (RW1)) 150 parts of polyester resin particle dispersion (APE1), 20 parts of release agent particle dispersion (WAX1), and 2.9 parts of anionic surfactant (Dowfax2A1 manufactured by The Dow Chemical Company) were mixed, and then 1.0% nitric acid was added at a temperature of 25°C to adjust the pH to 3.0, to obtain a mixed particle dispersion (RW1).

[0212] - Toner preparation - Polyester resin particle dispersion (APE1): 700 parts Colorant particle dispersion: 133 parts Ion-exchanged water: 400 parts Anionic surfactant (Dowfax2A1, manufactured by The Dow Chemical Company): 2.9 parts The above components were placed in a 3-liter reaction vessel equipped with a thermometer, a pH meter, and a stirrer, and 1.0% nitric acid was added at 25° C. to adjust the pH to 3.0. The mixture was then dispersed at 5,000 rpm with a homogenizer (Ultra Turrax T50, manufactured by IKA Japan Co., Ltd.) while 130 parts of the prepared aqueous aluminum sulfate solution was added and dispersed for 6 minutes.

[0213] Then, a stirrer and a mantle heater were installed in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was sufficiently stirred. The temperature was raised at a rate of 0.2°C / min up to 40°C, and at a rate of 0.05°C / min after exceeding 40°C, and the particle size was measured every 10 minutes using a Multisizer II (aperture diameter: 50μm, manufactured by Coulter). When the volume average particle size reached 5.0μm, the temperature was maintained, and 450 parts of the mixed particle dispersion (RW1) were added over 5 minutes. After maintaining for 30 minutes, the pH was adjusted to 9.0 using a 1% aqueous sodium hydroxide solution. Thereafter, the temperature was raised to 85°C at a rate of 1°C / min and maintained at that temperature, while adjusting the pH to 9.0 every 5°C. When the particle shape and surface properties were observed using an optical microscope and a scanning electron microscope (FE-SEM), the coalescence of the particles was confirmed at the 5.0th hour, so the vessel was cooled to 30°C over 5 minutes with cooling water.

[0214] The cooled slurry was passed through a nylon mesh with 15 μm openings to remove coarse powder, and the toner slurry that passed through the mesh was filtered under reduced pressure with an aspirator. The toner remaining on the filter paper was crushed finely by hand and added to ion-exchanged water with a temperature of 30° C. and 10 times the amount of the toner, and mixed and stirred for 30 minutes. The mixture was then filtered under reduced pressure with an aspirator, and the toner remaining on the filter paper was crushed finely by hand and added to ion-exchanged water with a temperature of 30° C. and 10 times the amount of the toner, and mixed and stirred for 30 minutes, and then filtered under reduced pressure with an aspirator again, and the electrical conductivity of the filtrate was measured. This operation was repeated until the electrical conductivity of the filtrate was 10 μS / cm or less, and the toner was washed. The washed toner was crushed finely with a wet-dry type granulator (Comil), and then vacuum-dried in an oven at 35° C. for 36 hours to obtain toner particles.

[0215] Then, 3.3 parts of silica particles were added as an external additive to 100 parts of toner particles. The mixture was then mixed for 3 minutes at a peripheral speed of 30 m / s using a Henschel mixer. The mixture was then sieved using a vibrating sieve with an opening of 45 μm to obtain a toner.

[0216] -Creating the carrier- 500 parts of spherical magnetite particle powder having a volume average particle size of 0.18 μm was put into a Henschel mixer and thoroughly stirred, after which 5 parts of a titanate coupling agent was added, the temperature was raised to 95° C., and the mixture was mixed and stirred for 30 minutes to obtain spherical magnetite particles coated with a titanate coupling agent. Next, 6 parts of phenol, 10 parts of 30% formalin, 500 parts of magnetite particles, 7 parts of 25% aqueous ammonia, and 400 parts of water were added to a 1L four-neck flask and mixed and stirred. Next, the mixture was heated to 90°C over 60 minutes while stirring, reacted at the same temperature for 180 minutes, cooled to 30°C, added with 500ml of water, removed the supernatant, and washed the precipitate with water. This was dried at 180°C under reduced pressure, and coarse powder was removed using a sieve with a mesh size of 106μm to obtain core particles with an average particle size of 38μm. Next, 200 parts of toluene and 35 parts of a styrene-methyl methacrylate copolymer (component molar ratio 10:90, weight average molecular weight 160,000) were stirred with a stirrer for 90 minutes to obtain a coating resin solution. 1000 parts of core particles and 70 parts of coating resin solution were placed in a vacuum degassing kneader coater (rotor-wall clearance 35 mm) and stirred at 30 rpm for 30 minutes while maintaining the temperature at 65°C. The temperature was then lowered to 88°C, and the mixture was depressurized to remove toluene, degass, and dried. The mixture was then passed through a mesh with 75 μm openings. The shape factor SF2 of the carrier was 104.

[0217] - Preparation of developer - A developer was prepared by mixing 8 parts of the toner and 100 parts of the carrier in a V blender.

[0218] - Toner properties - The ratio of the release agent present in the region within 800 nm from the surface of the toner particles to the release agent in the entire toner particles (surface layer ratio of the release agent) was measured by the above-mentioned method. Also, the melting temperature of the release agent was measured by the above-mentioned method.

[0219] <Cleaning Blade Production> Polycaprolactone polyol (Daicel Corporation, Plaxel 205, and polycaprolactone polyol (Daicel Corporation, Plaxel 240) were used as the hard segment material of the polyol component. In addition, an acrylic resin containing two or more hydroxyl groups (Soken Chemical & Engineering Co., Ltd., Actflow UMB-2005B) was used as the soft segment material, and the hard segment material and soft segment material were mixed in a ratio of 8:2 (mass ratio). Next, 4,4'-diphenylmethane diisocyanate (Millionate MT, manufactured by Nippon Polyurethane Industry Co., Ltd.) was added as an isocyanate compound to 100 parts of the mixture of the hard segment material and the soft segment material, and the mixture was reacted at 70°C for 3 hours under a nitrogen atmosphere. The above isocyanate compound was then further added, and the mixture was reacted at 70°C for 3 hours under a nitrogen atmosphere to obtain a prepolymer. Next, the prepolymer was heated to 100°C and degassed under reduced pressure for 1 hour. After that, a mixture of 1,4-butanediol and trimethylolpropane was added to the prepolymer and mixed for 3 minutes to prevent air bubbles from being introduced, to prepare a composition for forming a back layer. Next, the composition for forming a back layer was poured into a centrifugal molding machine and subjected to a curing reaction. After that, the composition was cut to a length of 15 mm and a thickness of 1.5 mm to form a back layer.

[0220] Next, an edge layer having a length of 15 mm and a thickness of 0.5 mm was formed in the same manner as for forming the back surface layer, except that the ratio of the hard segment material and the soft segment material was changed to 7:3 (mass ratio). The edge layer and the back layer were integrally molded during centrifugal molding. That is, the molten material of the back layer (composition for forming the back layer) was poured into a centrifugal molding machine and rotated, and before the composition for forming the back layer was completely solidified (while the material had tackiness), the molten material of the edge layer was poured into the centrifugal molding machine, and the material was solidified while rotating the centrifugal molding machine to be integrally molded, thereby obtaining a cleaning blade precursor.

[0221] -Contact area modification treatment The contact portion of the edge layer of the obtained cleaning blade precursor with the intermediate transfer belt was subjected to a surface modification treatment with a silicone-based polymer as follows. The silicone polymer used was Modiper FS770, a product of NOF Corp. The surface modification treatment was performed by immersing the cleaning blade precursor for 120 seconds in a surface treatment liquid prepared by dispersing and mixing 20 parts of 4,4'-diphenylmethane diisocyanate (4,4-MDI) and 2 parts of silicone polymer in 100 parts of methyl ethyl ketone (MEK) for 3 hours using a ball mill, and then removing and drying in an oven at 50°C.

[0222] By the above operations, a cleaning blade having a length of 15 mm and a thickness of 2 mm was obtained, which had a two-layer structure of an edge layer and a back layer, and the portion in contact with the intermediate transfer belt was surface-modified.

[0223] -Cleaning blade properties- In the cleaning blade, the hardness Ha (°) of the back layer, the hardness Hb (°) of the edge layer, the ratio (Hb / Ha), the ratio of the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt to the total amount of F and Si present within 5 μm from the surface (surface ratio of F, Si), the total amount of F and Si present on the surface of the edge layer that contacts the intermediate transfer belt (surface F, Si amount (atm %)), and the total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt (50 nm position F, Si amount (atm %)) were measured using the method described above.

[0224] <Preparation of intermediate transfer belt> Carbon black particles were dispersed in a polyamic acid solution to prepare coating solution 1. The coating solution was applied onto a cylindrical mold to form a coating film, which was then dried. (Substrate 1) Thereafter, another carbon black particle was dispersed in the polyamic acid solution to prepare a coating liquid 2, which was then coated onto the substrate 1 and dried. After that, the substrate was subjected to a firing process and then cut. By the above operations, a polyimide intermediate transfer belt was obtained.

[0225] <Image forming device> The electrostatic image developer, intermediate transfer belt, and cleaning blade for the intermediate transfer belt obtained above were attached to an image forming apparatus "FUJIFILM Business Innovation Co., Ltd. Apeosport-VI C7771." The attachment conditions for the cleaning blade for the intermediate transfer belt were as follows: pressing pressure NF (Normal Force, gf / mm) was set to the conditions shown in Table 1, and the angle W / A (Working Angle) was set to 10°.

[0226] [Examples 2 to 9, Comparative Examples 1 to 8] <Preparation of electrostatic image developer> In Example 1, a release agent used in preparing the release agent dispersion was selected, and the amount of the mixed particle dispersion (RW1) used in preparing the toner was adjusted to prepare toner particles that satisfied the "surface layer ratio (%) of the release agent" and "melting temperature (°C) of the release agent" shown in Tables 1 and 2, and an electrostatic image developer was obtained. As the release agents having the melting temperatures shown in Tables 1 and 2, the following were used alone or in combination. Paraffin wax (manufactured by Nippon Seiro Co., Ltd., melting temperature 64°C) Paraffin wax (HNP9 made by Nippon Seiro, melting temperature 75℃) Ester wax (NOF Corp., melting temperature 82°C) Fischer-Tropsch wax (FNP-0090 manufactured by Nippon Seiro Co., Ltd., melting temperature 90°C)

[0227] <Cleaning Blade Production> In Example 1, the ratio (mass ratio) of the hard segment material and the soft segment material when forming the edge layer and the back layer was adjusted, the treatment components used for the surface modification treatment of the contact portion of the edge layer of the obtained cleaning blade precursor with the intermediate transfer belt were selected, and the conditions of the concentration and immersion time of the surface modification treatment were adjusted to produce a cleaning blade that satisfies the "back layer hardness Ha (°)", "edge layer hardness Hb (°)", "Hb / Ha", "surface layer ratio of F,Si (%)", "surface F,Si amount (atm%)", and "50 nm position F,Si amount (atm%)" described in Tables 1 and 2. In addition, the pressing pressure NF (gf / mm) when mounting the obtained cleaning blade on the image forming apparatus was set to the conditions described in Tables 1 and 2. The blade treatment components shown in Tables 1 and 2 were as follows: Silicone polymer (NOF Corporation, Modiper FS770) Fluorine compounds (NOF Corporation, Modiper F206)

[0228] <Evaluation test> Using the image forming apparatus prepared in each of the Examples and Comparative Examples, 10,000 images with an image density of 1% were output in an environment of a temperature of 28° C. and a humidity of 80% RH.

[0229] -Evaluation of filming on intermediate transfer belt After the image was output, an observation image of the intermediate transfer belt surface of 100 μm square was binarized, the area ratio occupied by the deposits was calculated, and the image was evaluated according to the following criteria. G0: No adhesion (0% adhesion) G1: Slight adhesion (adhesion rate less than 1%) G2: Deposit ratio 1% to less than 3% G3: Deposit ratio 3% to less than 5% G4: Deposit ratio 5% to less than 10% G5: Deposit rate 10 or more

[0230] Staple mark The output image was checked for the presence or absence of staple marks and evaluated according to the following criteria. A(〇): No occurrence B(×): Occurred

[0231] The toner load on the image forming device with the fixing unit removed was 0.45 mg / cm 2 The unfixed image was output so that it was adjusted to the following: The recording medium used was A4 size OS coated W paper (basis weight 127 gsm) manufactured by Fujifilm Business Innovation Co., Ltd. The output image was an image with a size of 50 mm x 50 mm and an image density of 100%. The fixing evaluation device used was an ApeosPortIV C3370 manufactured by FUJIFILM Business Innovation Co., Ltd., with the fixing unit removed and modified to allow the nip pressure and fixing temperature to be changed. The process speed was set to 175 mm / sec, and the resulting fixed image was folded under a weight, and the image quality was evaluated based on the degree of image loss in that area. G1: No image defects were observed. G2: Image defects were observed, but were minor. G3: Slight image defects were observed, but within acceptable limits. G4: Image loss was observed

[0232] [Table 1]

[0233] [Table 2]

[0234] As shown in Tables 1 and 2, the image forming apparatus of this embodiment suppresses the occurrence of toner filming on the surface of the intermediate transfer belt and staple marks in the image, compared to the comparative example.

[0235] The present embodiment includes the following aspects. (((1))) An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; an intermediate transfer belt onto whose outer circumferential surface the toner image is transferred; a primary transfer means having a primary transfer member for primarily transferring the toner image formed on the surface of an image carrier onto an outer peripheral surface of the intermediate transfer belt; a secondary transfer unit having a secondary transfer member for secondarily transferring the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; a cleaning device having a cleaning blade which comes into contact with and cleans the outer peripheral surface of the intermediate transfer belt, the cleaning blade having a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer being made of polyurethane resin, the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer being 0.84 or more and 0.93 or less, and the total amount of F and Si present within 200 nm from the surface of the edge layer which comes into contact with the intermediate transfer belt being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising: (((2))) The image forming apparatus according to (((1))), wherein the amount of the release agent present in a region within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle. (((3))) The image forming apparatus according to (((1))) or (((2))), wherein the melting temperature of the release agent is 70° C. or higher and 75° C. or lower. (((4))) The image forming apparatus according to any one of (((1))) to (((3))), wherein the cleaning blade has a ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer of 0.87 or more and 0.90 or less. (((5))) The image forming apparatus according to any one of (((1))) to (((4))), wherein the hardness Hb of the edge layer is 75° or more and less than 85°, and the hardness Ha of the back layer is 85° or more and 95° or less. (((6))) The image forming apparatus according to (((5))), wherein the hardness Hb of the edge layer is 77° or more and 83° or less, and the hardness Ha of the back layer is 87° or more and 93° or less. (((7))) The image forming apparatus of any one of (((1))) to (((6))), wherein the total amount of F and Si present within 200 nm of the surface of the edge layer that contacts the intermediate transfer belt in the cleaning blade accounts for 85% or more of the total amount of F and Si present within 5 μm of the surface. (((8))) The image forming apparatus according to any one of (((1))) to (((7))), wherein the cleaning blade has an edge layer having a surface that comes into contact with the intermediate transfer belt having a total amount of F and Si of 5 atm % or more. (((9))) The image forming apparatus according to (((8))), wherein the cleaning blade has an edge layer having a surface that comes into contact with the intermediate transfer belt with a total amount of F and Si of 18 atm % or more and 25 atm % or less. (((10))) The image forming apparatus of any one of (((1))) to (((9))), wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt of 0.3 atm % or more. (((11))) The image forming apparatus according to (((10))), wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt of 0.3 atm % or more and 2.0 atm % or less. (((12))) The image forming apparatus according to any one of (((1))) to (((11))), wherein the cleaning blade contains a silicone-based polymer in a surface layer of the edge layer that comes into contact with the intermediate transfer belt. (((13))) The image forming apparatus according to any one of (((1))) to (((12))), wherein the cleaning blade contacts the intermediate transfer belt with a pressing pressure of 1.5 gf / mm or more and 3.5 gf / mm or less. (((14))) a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a primary transfer step of primarily transferring the toner image formed on the surface of an image carrier onto an outer peripheral surface of an intermediate transfer belt; a secondary transfer step of secondary transferring the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; a cleaning step of contacting an outer peripheral surface of the intermediate transfer belt with a cleaning blade having a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer being made of polyurethane resin, the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer being 0.84 or more and 0.93 or less, and the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising:

[0236] According to the invention of (((1))), there is provided an image forming apparatus in which the occurrence of toner filming on the surface of the intermediate transfer belt and the occurrence of staple marks in an image are suppressed, as compared to an image forming apparatus equipped with a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.84 or exceeds 0.93, or in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. According to the invention related to (((2))), an image forming apparatus is provided which has excellent low-temperature fixing ability of images compared to an image forming apparatus in which the release agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle. According to the invention related to (((3))), an image forming apparatus is provided which is superior in low-temperature image fixing ability compared to an image forming apparatus in which the melting temperature of the release agent is higher than 75°C, and an image forming apparatus is provided in which the occurrence of toner filming on the intermediate transfer belt surface is suppressed compared to an image forming apparatus in which the melting temperature of the release agent is lower than 70°C. According to the invention related to (((4))), there is provided an image forming apparatus in which the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed compared to an image forming apparatus equipped with a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.87 or exceeds 0.90. According to the invention relating to (((5))) or (((6))), an image forming apparatus is provided in which the occurrence of staple marks in an image is suppressed compared to an image forming apparatus equipped with a cleaning blade whose edge layer has a hardness of 85° or more or a cleaning blade whose back layer has a hardness of more than 95°, an image forming apparatus is provided in which excellent cleaning performance is achieved and wear of the cleaning blade is suppressed compared to an image forming apparatus equipped with a cleaning blade whose edge layer has a hardness of less than 75°, and an image forming apparatus is provided in which curling of the cleaning blade is suppressed compared to an image forming apparatus equipped with a cleaning blade whose back layer has a hardness of less than 85°. According to the invention related to (((7))), there is provided an image forming apparatus in which the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 85% of the total amount of F and Si present within 5 μm from the surface. According to the invention related to (((8))) or (((9))), an image forming apparatus is provided in which the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present on the surface of the edge layer that comes into contact with the intermediate transfer belt is less than 15 atm %. According to the invention related to (((10))) or (((11))), an image forming apparatus is provided in which the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed even over time, as compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt is less than 0.3 atm %. According to the invention related to (((12))), there is provided an image forming apparatus in which the surface layer of the edge layer that comes into contact with the intermediate transfer belt does not contain a silicone-based polymer, and in which the occurrence of toner filming on the surface of the intermediate transfer belt is suppressed compared to an image forming apparatus equipped with a cleaning blade that contains a fluorine-based compound. According to the invention pertaining to (((13))), an image forming apparatus is provided in which the occurrence of staple marks in an image is more suppressed than in an image forming apparatus in which a cleaning blade contacts the intermediate transfer belt with a pressing pressure of less than 1.5 gf / mm or more than 3.5 gf / mm, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the intermediate transfer belt is more suppressed than in an image forming apparatus in which a cleaning blade contacts the intermediate transfer belt with a pressing pressure of less than 1.5 gf / mm or more than 3.5 gf / mm. According to the invention of (((14))), there is provided an image forming method which suppresses the occurrence of toner filming on the surface of the intermediate transfer belt and staple marks in an image, as compared to an image forming method having a cleaning step using a cleaning blade in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.85 or exceeds 0.93, or a cleaning blade in which the total amount of F and Si present within 200 nm from the surface of the edge layer that comes into contact with the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Explanation of symbols]

[0237] 1Y, 1M, 1C, 1K Image forming unit 10 Primary transfer section 11 Photoreceptor 12 Charger 13 Laser exposure device 14 Developer 15 Intermediate transfer belt 16 Primary transfer roll 17 Photoconductor cleaner 20 Secondary transfer section 22 Secondary transfer roll 22A Secondary transfer roll cleaning member 25 Back roll 26 Power supply roll 31 Driving Roll 32 Support roll 33 Tensioning roll 34 Cleaning back roll 35 Intermediate transfer belt cleaning blade 40 Control section 42 Reference Sensor 43 Image density sensor 50 Paper storage section 51 Paper feed roll 52 Transport roll 53 Transport guide 55 Conveyor belt 56 Fixing entrance guide 60 Fixing device 100 Image forming device

Claims

1. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; an intermediate transfer belt onto whose outer circumferential surface the toner image is transferred; a primary transfer means having a primary transfer member for primarily transferring the toner image formed on the surface of an image carrier onto an outer peripheral surface of the intermediate transfer belt; a secondary transfer unit having a secondary transfer member for secondarily transferring the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; a cleaning device having a cleaning blade which comes into contact with and cleans the outer peripheral surface of the intermediate transfer belt, the cleaning blade having a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer being made of polyurethane resin, a ratio (Hb / Ha) of a hardness Hb of the edge layer to a hardness Ha of the back layer being 0.84 or more and 0.93 or less, and a total amount of F and Si present within 200 nm from a surface of the edge layer which comes into contact with the intermediate transfer belt accounting for 75% or more of a total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising:

2. 2. The image forming apparatus according to claim 1, wherein the amount of the release agent present in a region within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle.

3. 2. The image forming apparatus according to claim 1, wherein the release agent has a melting temperature of 70[deg.] C. or higher and 75[deg.] C. or lower.

4. 2 . The image forming apparatus according to claim 1 , wherein the cleaning blade has a ratio (Hb / Ha) of a hardness Hb of the edge layer to a hardness Ha of the back layer of 0.87 or more and 0.90 or less.

5. 2. The image forming apparatus according to claim 1, wherein the hardness Hb of the edge layer is equal to or greater than 75 degrees and less than 85 degrees, and the hardness Ha of the back layer is equal to or greater than 85 degrees and less than 95 degrees.

6. 6. The image forming apparatus according to claim 5, wherein the hardness Hb of the edge layer is 77 degrees or more and 83 degrees or less, and the hardness Ha of the back layer is 87 degrees or more and 93 degrees or less.

7. 2. The image forming apparatus according to claim 1, wherein the total amount of F and Si present within 200 nm of the surface of the edge layer that contacts the intermediate transfer belt accounts for 85% or more of the total amount of F and Si present within 5 μm of the surface.

8. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has an edge layer having a surface contacting the intermediate transfer belt, the surface having an F and Si content of 15 atm % or more in total.

9. 9. The image forming apparatus according to claim 8, wherein the cleaning blade has an edge layer having a surface that contacts the intermediate transfer belt and a total amount of F and Si present thereon is 18 atm % or more and 25 atm % or less.

10. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt of 0.3 atm % or more.

11. 11. The image forming apparatus according to claim 10, wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface of the edge layer that contacts the intermediate transfer belt of 0.3 atm % or more and 2.0 atm % or less.

12. The image forming apparatus according to claim 1 , wherein the cleaning blade includes a surface layer of the edge layer that contacts the intermediate transfer belt and contains a silicone-based polymer.

13. 2. The image forming apparatus according to claim 1, wherein the cleaning blade contacts the intermediate transfer belt with a pressing pressure of 1.5 gf / mm or more and 3.5 gf / mm or less.

14. a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a primary transfer step of primarily transferring the toner image formed on the surface of an image carrier onto an outer peripheral surface of an intermediate transfer belt; a secondary transfer step of secondary transferring the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; a cleaning step of contacting an outer peripheral surface of the intermediate transfer belt with a cleaning blade having a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer being made of polyurethane resin, a ratio (Hb / Ha) of a hardness Hb (°) of the edge layer to a hardness Ha (°) of the back layer being 0.84 or more and 0.93 or less, and a total amount of F and Si present within 200 nm from a surface of the edge layer that contacts the intermediate transfer belt accounting for 75% or more of a total amount of F and Si present within 5 μm from the surface; An image forming method comprising:

Citation Information

Patent Citations

  • Cleaning blade

    JP2001051565A

  • Image forming apparatus and process cartridge

    JP2009300751A

  • Process cartridge, image forming apparatus, and image forming method

    JP2021012342A